Linear high density polyethylene composition and rotomolded article
The polyethylene composition prepared by the dual-reactor method solves the problem of balancing toughness, stiffness and processability in rotational molding applications, and realizes a high-density, high melt index polyethylene composition, which is suitable for manufacturing large and/or thick rotational molding parts and has good environmental resistance and processing performance.
Patent Information
- Application Number
- CN202480028187.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-04-24
- Filing Date
- 2024-04-19
- Publication Date
- 2026-01-06
AI Technical Summary
Existing polyethylene resins are difficult to simultaneously achieve good toughness, stiffness, environmental resistance and processability in rotational molding applications, especially when manufacturing large and/or thick rotational molded parts, where problems such as bubble formation and excessive flow exist.
A two-reactor method was used to prepare two ethylene copolymers using metallocene catalysts and Ziegler-Natta catalysts, respectively. By combining specific molecular weight distributions and short chain branching ratios, a polyethylene composition with high density and moderate melt index was formed. The copolymers were then combined by solution polymerization to prepare a polyethylene composition suitable for rotational molding.
It achieves a balance of high toughness, ESCR properties and good processability in rotational molding applications, prevents excessive flow of large and/or thick rotational molding parts during long heating cycles, and ensures the densification and mechanical properties of the products.
Smart Images

Figure CN121285583A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to polyethylene compositions suitable for use in rotational molding articles. The invention also relates to solution polymerization methods for preparing polyethylene compositions. The invention further relates to rotational molding articles, particularly but not limited to large and thick rotational molding parts, for example, for use in large tanks. Background Technology
[0002] Rotational molding (also known as rotomolding) is used to manufacture hollow plastic products. The method is typically described in four steps: (1) loading a polymer (usually in the form of a solid powder); (2) slowly rotating a mold biaxially while heating the powder to form a homogeneous melt; (3) cooling and solidifying the melt; and (4) unloading the plastic part from the mold. A biaxially rotating mold is necessary in steps (2) and (3) of this method.
[0003] In rotational molding, the material is subjected to high temperatures for a relatively long period to allow the powder particles to melt, deposit, and fully densify. Melt solidification along the thickness of the molded part is gradual and non-uniform. Resin design needs to consider the material's ability to rapidly sinter and densify, demonstrate good thermal stability, and exhibit optimal crystallization behavior in terms of mechanical properties and dimensional stability (see Rao et al., Polymer Engineering and Science
[1972] , Vol. 12, No. 4, pp. 237-264).
[0004] A relatively low rotational speed is applied to the mold, typically ranging from 4 to 30 rpm. This process involves the gradual melting of plastic powder, starting in a layer adjacent to the mold surface and progressing towards the free interior surface that will become a hollow plastic part. Once a layer of particles has adhered to the mold surface and undergone the melt transition, it undergoes a surface energy-driven coalescence process (sintering). During the powder deposition process, sporadic air particles are trapped between the particles, eventually forming bubbles. These bubbles then slowly dissipate as gases dissolve in the melt. To ensure the formation of bubble-free molded parts, it is crucial to minimize the size of the bubbles initially formed during powder densification. This is accomplished by ensuring rapid coalescence between individual particles. Coalescence is driven by surface energy, but slower for resins with higher viscosity and relative elasticity. The polymer undergoes a very low rate of deformation during this transition. Accordingly, the most relevant rheological properties are viscosity at low shear (zero shear viscosity), temperature dependence of viscosity (especially in the range above but close to the melt transition temperature), and relative elasticity of the material.
[0005] The relevant rheological parameters of rotational molding are described in, for example, (a) Bellehumeur et al., Polymer Engineering and Science
[1996] , Vol. 36, No. 17, pp. 2198-2207; (b) Bellehumeur et al., Rheologica Acta
[1998] , Vol. 37, pp. 270-278; and (c) Wang et al., Polymer Engineering and Science
[2004] , Vol. 44, No. 9, pp. 1662-1669.
[0006] The evaluation of relative elasticity is based on measurements taken at low frequencies, which are most relevant to the conditions associated with powder sintering and densification in rotational molding. Relative elasticity can be evaluated based on the ratio of G' to G” at a frequency of 0.05 rad / s from DMA frequency scan measurements taken at 190 °C. Data reported in the literature show that resin compositions with high relative elasticity tend to exhibit processing difficulties in terms of slow powder densification. Wang et al.
[2004] reported sufficient rotational molding properties for blends characterized as having a relative elasticity as high as 0.125. In this study, the effect of plastite content on the rotational molding properties of polypropylene was investigated. Further analysis of the results published by Wang et al. showed that compositions with higher plastite content exhibited improved relative elasticity (G' / G”>0.13) and a correspondingly increased difficulty in achieving full densification during rotational molding evaluation.
[0007] When developing thermoplastic resins suitable for use in the preparation of molded articles (e.g., rotational molding articles), some key considerations include resistance to environmental stress over time (e.g., resistance to environmental stress cracking [ESCR]), impact resistance (e.g., cantilever beam impact test performance), and processability (rheology suitable for rotational molding applications).
[0008] Although several polyethylene resins suitable for use in molded parts have been developed, improvements are still needed, especially for resins used to manufacture large and / or thick rotational molded parts (e.g., for use in large tanks).
[0009] For example, US 7022770 discloses ESCR properties of polyethylene compositions suitable for use in molded articles, but does not teach how to achieve a balance between ESCR properties and processability.
[0010] Meanwhile, US 10808053 teaches that a reverse comonomer distribution is beneficial for molding applications and discloses embodiments containing long-chain branches. However, the embodiments are limited to densities less than 0.930 g / cm³. 3 The composition, and its performance was observed only in membrane applications.
[0011] US 8076421 discloses compositions based on very low molecular weight fractions (GPC-RI) and very high molecular weight fractions (GPC-LC), but the examples are limited to membrane applications.
[0012] US 8101687 describes a multimodal ethylene copolymer and specifies that a low molecular weight component is a heterogeneous ethylene interpolymer. The composition exhibits good stress cracking resistance and is suitable for use in piping. However, the upper limit of the melt flow index is 1.0 g / 10 min.
[0013] US 9169337 also describes resins with low melt flow index (less than 1.5 g / 10 min), specifically bimodal compositions with enhanced ESCR for blow molding applications. These compositions have relatively high molecular weights and relatively broad molecular weight distributions.
[0014] In addition, US 8492498 discloses compositions with high ESCR, but is limited to those with a primary structural parameter (PSP2) greater than 8.9.
[0015] There is still a need for new polyethylene resins that can be used in rotational molding applications, exhibiting good stiffness and toughness, as well as environmental resistance, while maintaining good processability.
[0016] The present invention was created based on the above considerations. Invention Overview A first aspect of the present invention is a polyethylene composition comprising: (i) 10-60% by weight of a first ethylene copolymer with a density of 0.880-0.930 g / cm³ 3 Molecular weight distribution (M w / M n The weight-average molecular weight (M) is 1.7-2.7. w The concentration is 140,000-250,000 g / mol; (ii) 90-40% by weight of a second ethylene copolymer with a density of 0.940-0.975 g / cm³ 3 Molecular weight distribution (M w / M n The molecular weight is 2.0-3.3, and the weight-average molecular weight (M) is... w The concentration is 20,000-90,000 g / mol; The ratio of the number of short chain branches per thousand carbon atoms in the first ethylene copolymer to the number of short chain branches per thousand carbon atoms in the second ethylene copolymer (SCB1 / SCB2) is at least 5.0. The polyethylene composition has a density of at least 0.940 g / cm³. 3 Melt index (I2) less than 3.0 g / 10 min, melt flow ratio (I 21 / I2) is at most 60, and the long-chain branching factor (LCBF) is at most 0.0400; and The weight percentage of the first ethylene copolymer or the second ethylene copolymer is defined as the weight of the first copolymer or the second copolymer divided by the sum of the weights of the first ethylene copolymer and the second ethylene copolymer, and then multiplied by 100.
[0018] The present invention provides a density of at least 0.940 g / cm³. 3 Polyethylene compositions with a melt index of 1.0-3.0 g / 10min or less than 3.0 g / 10min are suitable for molding applications (especially rotational molding) and exhibit high toughness and ESCR properties. These compositions are advantageous for manufacturing large and / or thick rotational molded parts (e.g., for use in large tanks) because they offer an unusual combination of properties (toughness, stiffness, ESCR) and processability (rheology). The compositions have a high comonomer content and a reverse comonomer distribution. The compositions also contain a limited amount of long-chain branching, which results in a higher zero-shear viscosity and higher flow resistance at low deformation rates. This is advantageous in preventing overflow during the manufacture of large and / or thick rotational molded parts, especially since the heating cycles for such parts may be long, and thus the resin carries a higher risk of excessive melt flow restriction.
[0019] A second aspect of the present invention is a solution polymerization method for preparing a polyethylene composition; wherein the polymerization method includes: In the first reactor, ethylene is polymerized with α-olefins using a metallocene catalyst; and In the second reactor, ethylene is polymerized with α-olefins using a Ziegler-Natta catalyst. The first reactor and the second reactor are connected in series; and the polyethylene composition comprises: (i) 10-60% by weight of a first ethylene copolymer with a density of 0.880-0.930 g / cm³ 3 Molecular weight distribution (M w / M n The weight-average molecular weight (M) is 1.7-2.7. w The concentration is 140,000-250,000 g / mol; (ii) 90-40% by weight of a second ethylene copolymer with a density of 0.940-0.975 g / cm³ 3 Molecular weight distribution (M w / M n The molecular weight is 2.0-3.3, and the weight-average molecular weight (M) is...w The concentration is 20,000-90,000 g / mol; The ratio of the number of short chain branches per thousand carbon atoms in the first ethylene copolymer to the number of short chain branches per thousand carbon atoms in the second ethylene copolymer (SCB1 / SCB2) is at least 5.0. The polyethylene composition has a density of at least 0.940 g / cm³. 3 Melt index (I2) less than 3.0 g / 10 min, melt flow ratio (I 21 / I2) is at most 60, and the long-chain branching factor (LCBF) is at most 0.0400; and The weight percentage of the first ethylene copolymer or the second ethylene copolymer is defined as the weight of the first copolymer or the second copolymer divided by the sum of the weights of the first ethylene copolymer and the second ethylene copolymer, and then multiplied by 100.
[0020] Therefore, the second aspect provides a solution polymerization method for preparing the polyethylene composition of the first aspect.
[0021] Appropriately, the second approach is the two-reactor method.
[0022] A third aspect of the present invention is a rotationally molded article prepared from a polyethylene composition comprising: (i) 10-60% by weight of a first ethylene copolymer with a density of 0.880-0.930 g / cm³ 3 Molecular weight distribution (M w / M n The weight-average molecular weight (M) is 1.7-2.7. w The concentration is 140,000-250,000 g / mol; (ii) 90-40% by weight of a second ethylene copolymer with a density of 0.940-0.975 g / cm³ 3 Molecular weight distribution (M w / M n The molecular weight is 2.0-3.3, and the weight-average molecular weight (M) is... w The concentration is 20,000-90,000 g / mol; The ratio of the number of short chain branches per thousand carbon atoms in the first ethylene copolymer to the number of short chain branches per thousand carbon atoms in the second ethylene copolymer (SCB1 / SCB2) is at least 5.0. The polyethylene composition has a density of at least 0.940 g / cm³. 3 Melt index (I2) less than 3.0 g / 10 min, melt flow ratio (I 21 / I2) is at most 60, and the long-chain branching factor (LCBF) is at most 0.0400; and The weight percentage of the first ethylene copolymer or the second ethylene copolymer is defined as the weight of the first copolymer or the second copolymer divided by the sum of the weights of the first ethylene copolymer and the second ethylene copolymer, and then multiplied by 100.
[0023] Therefore, the third aspect provides a rotationally molded article prepared from the polyethylene composition of the first aspect.
[0024] The present invention includes combinations of the described aspects and preferred features, except where such combinations are clearly not permitted or explicitly avoided. Brief description of the attached diagram The embodiments and experiments illustrating the principles of the present invention will now be discussed with reference to the accompanying drawings, in which: Figure 1 Temperature elution fractionation curves obtained from TREF-CEF for Invention Examples 1-3 and Comparative Examples 7, 12 and 13 are shown. Figure 2 The molecular weight distribution and comonomer distribution from GPC-FTIR measurements are shown (Examples 1-3 of the invention and Comparative Examples 15 and 16 are shown in Figure A, and Example 3 of the invention and Comparative Examples 7 and 10-13 are shown in Figure B). Figure 3 The complex viscosity curves obtained from DMA frequency scans at 190°C for the inventive example and several comparative examples are shown (Figures A, B and C), as well as the zero shear viscosity vs. weight-average molecular weight estimated by the Ellis model (Figure D). Figure 4 The ESCR results (Figure A) and cantilever beam impact (Figure B) under condition A100 are shown, each plotted relative to the flexural secant modulus. Figure 5 The results of tests performed on the rotomolded specimens are shown – specifically, the mean ARM impact failure energy at −40°C (Figs. A and B), the ductility at −40°C (Figs. C and D), and the difference between the original rotomolded density and the sheet density (Figs. E and F).
[0026] Implementation Plan Description Aspects and embodiments of the invention will now be discussed with reference to the accompanying drawings. Further aspects and embodiments will be apparent to those skilled in the art. All documents mentioned herein are incorporated by reference.
[0027] Terminology Definition Except as indicated in the embodiments or elsewhere, all numerical values or expressions of amounts of ingredients, preparation conditions, etc., used in the specification and claims should be understood to be modified by the term "about" in all cases. Therefore, unless indicated to the contrary, the numerical parameters set forth in the following specification and appended claims are approximate values and may vary depending on the desired properties expected to be obtained from various embodiments. At least and without attempt to limit the application of the doctrine of equivalence to the scope of the claims, each numerical parameter should be interpreted at least according to the number of significant figures reported and by applying common rounding techniques. The numerical values set forth in the specific embodiments are reported as accurately as possible. However, any numerical value inherently contains some error necessarily caused by the standard deviation found in its respective test measurements.
[0028] It should be understood that any numerical range described herein is intended to include all subranges included therein. For example, the range "1-10" is intended to include all subranges between the stated minimum value 1 and the stated maximum value 10, and includes both the stated minimum value 1 and the stated maximum value 10; that is, the minimum value is equal to or greater than 1 and the maximum value is equal to or less than 10. Because the disclosed numerical ranges are continuous, they include every value between the minimum and maximum values. Unless otherwise expressly indicated, the various numerical ranges specified in this application are approximate values.
[0029] All composition ranges expressed herein are limited to totals of 100% (volume or weight percentage). When multiple components may be present in a composition, the maximum sum of the amounts of the components may exceed 100%, but it should be understood, and as will be readily apparent to those skilled in the art, that the amounts of the components actually used will conform to the maximum of 100%.
[0030] To form a more complete understanding of this disclosure, the following terms are defined and should be used in conjunction with the accompanying drawings and the description of the various embodiments throughout.
[0031] As used in this article, the term "monomer" refers to a small molecule that can chemically react with itself or other monomers to form chemical bonds and thus form a polymer.
[0032] As used herein, the terms “α-olefin” or “alpha olefin” are used to describe monomers having a linear hydrocarbon chain containing 3-20 carbon atoms with a double bond at one end of the chain; the equivalent term is “linear α-olefin”.
[0033] As used herein, the terms “polyethylene” or “ethylene polymer” refer to macromolecules produced from ethylene monomers and optionally one or more other monomers, regardless of the specific catalyst or method used to prepare the ethylene polymer.
[0034] With regard to the terms “ethylene homopolymer” or “polyethylene homopolymer”, it is indicated that the polymer referred to is the product of a polymerization method in which only ethylene is intentionally added or intentionally present as a polymerizable monomer.
[0035] With regard to the terms “ethylene copolymer” or “polyethylene copolymer”, it means that the polymer referred to is the product of a polymerization method in which ethylene and one or more α-olefins are intentionally added or intentionally present as polymerizable monomers.
[0036] The term "long-chain branching" or "long-chain branching" differs from short-chain branching because it is a macromolecule in nature and can, for example, have a length similar to that of the polymer backbone (to which the long-chain branching connects).
[0037] As used herein, the term "unsubstituted" means that a hydrogen group is bonded to a molecular group following the term "unsubstituted". The term "substituted" means that the group following the term has a portion (non-hydrogen group) having one or more hydrogen groups that have substituted one or more hydrogen groups at any position within the group; non-limiting examples of such portions include halogen groups (F, Cl, Br), hydroxyl, carbonyl, carboxyl, silyl, amine, phosphine, alkoxy, phenyl, naphthyl, C1-C 30 Alkyl, C2-C 30 Alkenyl groups and combinations thereof. Non-limiting examples of substituted alkyl and aryl groups include: acyl, alkylsilyl, alkylamino, alkoxy, aryloxy, alkylthio, dialkylamino, alkoxycarbonyl, aryloxycarbonyl, carbamoyl, alkylcarbamoyl and dialkylcarbamoyl, acyloxy, acylamino, arylamino and combinations thereof.
[0038] As used herein, the term "hydrocarbyl (hydrocarbyl radical or hydrocarbyl group)" refers to a straight-chain or cyclic aliphatic group, alkene group, alkynyl group, and aryl (aromatic) group that contains hydrogen and carbon but lacks one hydrogen atom.
[0039] As used herein, "alkyl" includes straight-chain alkane groups, branched alkane groups, and cyclic alkane groups lacking one hydrogen group; non-limiting examples include methyl (-CH3) and ethyl (-CH2CH3). The term "alkenyl" refers to linear, branched, and cyclic hydrocarbons containing at least one carbon-carbon double bond lacking one hydrogen group.
[0040] As used herein, the term "aryl" includes phenyl, naphthyl, pyridyl, and other groups whose molecules have an aromatic ring structure; non-limiting examples include naphthalene, phenanthrene, and anthracene. "Arylalkyl" is an alkyl group having an aryl group dangling from it; non-limiting examples include benzyl, phenethyl, and tolylmethyl; "alkylaryl" is an aryl group having one or more alkyl groups dangling from it; non-limiting examples include tolyl, xylyl, mesitylene, and cumyl.
[0041] As used herein, the term "heteroatom" includes any atom other than carbon and hydrogen that can bond with carbon. A "heteroatom-containing group" is a hydrocarbon group that contains heteroatoms and may contain one or more identical or different heteroatoms. In some embodiments, a heteroatom-containing group is a hydrocarbon group containing 1-3 atoms selected from boron, aluminum, silicon, germanium, nitrogen, phosphorus, oxygen, and sulfur. Non-limiting examples of heteroatom-containing groups include groups of imines, amines, oxides, phosphine, ethers, ketones, oxazoline heterocycles, oxazolines, thioethers, and the like. The term "heterocycle" refers to a ring system having a carbon skeleton containing 1-3 atoms selected from boron, aluminum, silicon, germanium, nitrogen, phosphorus, oxygen, and sulfur.
[0042] This disclosure provides a polyethylene composition comprising two components: (i) a first ethylene copolymer and (ii) a second ethylene copolymer different from the first ethylene copolymer.
[0043] In some embodiments, the polyethylene composition is used to manufacture molded articles.
[0044] In some embodiments, the polyethylene composition is used to manufacture rotationally molded articles.
[0045] In some embodiments, the polyethylene composition is used to manufacture compression-molded or injection-molded articles.
[0046] In some embodiments, the polyethylene composition is used for manufacturing blown films.
[0047] First ethylene copolymer In some embodiments, the first ethylene copolymer comprises both polymeric ethylene and at least one polymeric α-olefin comonomer, wherein polymeric ethylene is the predominant material.
[0048] In some embodiments, the α-olefin that can be copolymerized with ethylene to prepare the first ethylene copolymer can be selected from 1-propylene, 1-butene, 1-pentene, 1-hexene, and 1-octene, and mixtures thereof.
[0049] In some embodiments, a single-point catalyst is used to prepare the first ethylene copolymer. Non-limiting examples of single-point catalysts include phosphine-imine catalysts, metallocene catalysts, and confined geometry catalysts, all of which are well known in the art.
[0050] In some implementations, a single-point polymerization catalyst is used in a solution-phase polymerization method to prepare the first ethylene copolymer.
[0051] In some implementations, a unit site catalyst with hafnium (Hf) as the active metal center is used to prepare the first ethylene copolymer.
[0052] In some implementations, the first ethylene copolymer is an ethylene / 1-octene copolymer.
[0053] In some implementations, a metallocene catalyst is used to prepare the first ethylene copolymer.
[0054] In some implementations, a bridged metallocene catalyst is used to prepare the first ethylene copolymer.
[0055] In some implementations, a bridged metallocene catalyst having Formula I is used to prepare the first ethylene copolymer: (I) In formula (I): M is a Group 4 metal selected from titanium, zirconium, or hafnium; G is a Group 14 element selected from carbon, silicon, germanium, tin, or lead; R1 is a hydrogen atom, C 1-20 hydrocarbon group, C 1-20 Alkoxy or C 6-10 aryl oxide radical; R2 and R3 are independently selected from hydrogen and C atoms. 1-20 hydrocarbon group, C 1-20 Alkoxy or C 6-10 Aryloxy group; R4 and R5 are independently selected from hydrogen atoms and unsubstituted C atoms. 1-20 Hydrocarbon group, substituted C 1-20 hydrocarbon group, C 1-20 Alkoxy or C 6-10 Aryloxy group; and Q is an independently activatable leaving group ligand.
[0056] In some implementations, G stands for carbon.
[0057] In some implementations, R4 and R5 are independently aryl groups.
[0058] In some implementations, R4 and R5 are independently phenyl or substituted phenyl.
[0059] In some implementations, R4 and R5 are phenyl groups.
[0060] In some implementations, R4 and R5 are independently substituted phenyl groups.
[0061] In some embodiments, R4 and R5 are substituted phenyl groups, wherein the phenyl group is replaced by a substituted silyl group.
[0062] In some embodiments, R4 and R5 are substituted phenyl groups, wherein the phenyl group is replaced by a trialkylsilyl group.
[0063] In some embodiments, R4 and R5 are substituted phenyl groups, wherein the phenyl group is substituted at the para-position with a trialkylsilyl group. In one embodiment, R4 and R5 are substituted phenyl groups, wherein the phenyl group is substituted at the para-position with a trimethylsilyl group. In one embodiment, R4 and R5 are substituted phenyl groups, wherein the phenyl group is substituted at the para-position with a triethylsilyl group.
[0064] In some implementations, R4 and R5 are independently alkyl groups.
[0065] In some implementations, R4 and R5 are independently alkenyl groups.
[0066] In some implementations, R1 is hydrogen.
[0067] In some implementations, R1 is an alkyl group.
[0068] In some implementations, R1 is an aryl group.
[0069] In some implementations, R1 is an alkenyl group.
[0070] In some implementations, R2 and R3 are independently hydrocarbon groups having 1-30 carbon atoms.
[0071] In some implementations, R2 and R3 are independently aryl groups.
[0072] In some implementations, R2 and R3 are independently alkyl groups.
[0073] In some implementations, R2 and R3 are independently alkyl groups having 1-20 carbon atoms.
[0074] In some implementations, R2 and R3 are independently phenyl or substituted phenyl.
[0075] In some implementations, R2 and R3 are tert-butyl.
[0076] In some implementations, R2 and R3 are hydrogen.
[0077] In some implementations, M stands for hafnium (Hf).
[0078] In some implementations, a bridged metallocene catalyst having Formula I is used to prepare the first ethylene copolymer: (I) In (I): G is a Group 14 element selected from carbon, silicon, germanium, tin, or lead; R1 is a hydrogen atom, C 1-20 hydrocarbon group, C 1-20 Alkoxy or C6-10 Aryloxy group; R2 and R3 are independently selected from hydrogen atom, C 1-20 hydrocarbon group, C 1-20 Alkoxy or C 6-10 Aryloxy group; R4 and R5 are independently selected from hydrogen atoms and unsubstituted C atoms. 1-20 Hydrocarbon group, substituted C 1-20 hydrocarbon group, C 1-20 Alkoxy or C 6-10 Aryloxy group; and Q is an independently activatable leaving group ligand.
[0079] In this disclosure, the term "activatable" means that ligand Q can be cleaved from metal center M via a proton dissociation reaction or abstracted from metal center M by a suitable acidic or electrophilic activator compound (also called a "co-catalyst" compound) (examples of which are described below). The activatable ligand Q can also be converted into another ligand that is cleaved or abstracted from metal center M (e.g., a halide ion can be converted into an alkyl group). Not wishing to be bound by any single theory, the proton dissociation or abstraction reaction generates an active "cationic" metal center, which can polymerize olefins.
[0080] In some implementations, the activatable ligand Q is independently selected from hydrogen atoms; halogen atoms; C atoms. 1-20 hydrocarbon group, C 1-20 Alkoxy and C 6-10 Aryl or aryloxy, wherein the hydrocarbon group, alkoxy group, aryl group, or aryloxy group may each be unsubstituted or further substituted by one or more halogen or other groups; C 1-8 Alkyl; C 1-8 Alkoxy; C 6-10 Aryl or aryloxy; amido or phosphido, but wherein Q is not cyclopentadienyl. Two Q ligands can also be linked to each other to form, for example, substituted or unsubstituted diene ligands (e.g., 1,3-butadiene); or groups containing delocalized heteroatoms, such as acetate or acetamidinate. In a convenient embodiment of this disclosure, each Q is independently selected from halogen atoms, C... 1-4 Alkyl and benzyl groups. Particularly suitable activatable ligands Q are monoanionic, such as halide ions (e.g., chloride ions) or hydrocarbon groups (e.g., methyl, benzyl).
[0081] In some embodiments, the unit site catalyst used to prepare the first ethylene copolymer is diphenylmethylene (cyclopentadienyl) (2,7-di-tert-butylfluorenyl) hafnium dichloride with the molecular formula [(2,7-tBu2Flu)Ph2C(Cp)HfCl2].
[0082] In some embodiments, the unit site catalyst used to prepare the first ethylene copolymer is diphenylmethylene (cyclopentadienyl) (2,7-di-tert-butylfluorenyl)dimethylhafnium with the molecular formula [(2,7-tBu2Flu)Ph2C(Cp)HfMe2].
[0083] In addition to the single-site catalyst molecule itself, the active single-site catalyst system may further include one or more of the following: alkylaluminoxane co-catalysts and ion activators. The single-site catalyst system may also optionally include hindered phenols.
[0084] Although the exact structure of alkylaluminoxanes has not been determined, subject matter experts generally agree that they are a class of oligomers containing repeating units of the following general formula: (R)2AlO-(Al(R)-O) n -Al(R)2 The R groups can be the same or different straight-chain hydrocarbon groups, branched hydrocarbon groups, or cyclic hydrocarbon groups containing 1-20 carbon atoms, and n is 0-about 50. A non-limiting example of an alkylaluminoxane is methylaluminoxane (or MAO), wherein each R group is methyl.
[0085] In some embodiments, R in alkylaluminoxane is methyl, and m is 10-40.
[0086] In some implementations, the cocatalyst is modified methylaluminoxane (MMAO).
[0087] It is well known in the art that alkylaluminoxanes can act as both alkylating agents and activators. Therefore, alkylaluminoxane cocatalysts are often used in combination with activatable ligands such as halogens.
[0088] Generally, ion activators consist of a cation and a bulky anion; the latter is essentially noncoordinate. A non-limiting example of an ion activator is a tetracoordinate boron ion activator having four ligands bonded to a boron atom. Non-limiting examples of boron ion activators include those shown below: [R 5 ] + [B(R 7 )4] - Where B represents a boron atom, R 5 It is an aromatic hydrocarbon group (e.g., triphenylmethyl cation), and each R 7 The carbon atoms are independently selected from phenyl groups, which are either unsubstituted or substituted with 3-5 carbon atoms selected from fluorine atoms. 1-4 Alkyl or alkoxy substituents; and the formula -Si(R) 9 )3 silyl groups, wherein each R 9Independently selected from hydrogen and C atoms 1-4 Alkyl groups, and [(R 8 ) t ZH] + [B(R 7 )4] - Where B is a boron atom, H is a hydrogen atom, Z is a nitrogen or phosphorus atom, t is 2 or 3, and R 8 Selected from C 1-8 Alkyl, unsubstituted phenyl, or with at most three carbon atoms 1-4 Alkyl-substituted phenyl, or an R 8 Together with a nitrogen atom, it can form a phenylamine group, and R 7 As defined above.
[0089] In both equations, R 7 Non-limiting examples are pentafluorophenyl. Generally, boron ion activators can be described as salts of tetra(perfluorophenyl)boron; non-limiting examples include phenylammonium salts, carbium salts, oxonium salts, phosphonium salts, and sulfonium salts of tetra(perfluorophenyl)boron with phenylammonium and triphenylmethyl (or triphenylmethylonium). Further non-limiting examples of ion activators include: triethylammonium tetra(phenyl)boron, tripropylammonium tetra(phenyl)boron, tri-n-butylammonium tetra(phenyl)boron, trimethylammonium tetra(p-tolyl)boron, trimethylammonium tetra(o-tolyl)boron, tributylammonium tetra(pentafluorophenyl)boron, tripropylammonium tetra(o,p-dimethylphenyl)boron, tributylammonium tetra(m,m-dimethylphenyl)boron, tributylammonium tetra(p-trifluoromethylphenyl)boron, tributylammonium tetra(pentafluorophenyl)boron, tri... (n-Butyl)ammonium tetra(o-tolyl)boron, N,N-dimethylphenylammonium tetra(phenyl)boron, N,N-diethylphenylammonium tetra(phenyl)boron, N,N-diethylphenylammonium tetra(phenyl)n-butylboron, N,N-2,4,6-pentamethylphenylammonium tetra(phenyl)boron, di(isopropyl)ammonium tetra(pentafluorophenyl)boron, dicyclohexylammonium tetra(phenyl)boron, triphenylphosphonium tetra(phenyl)boron, tri(methylphenyl)phosphonium tetra(phenyl)boron, tri(dimethylphenyl)phosphonium tetra(phenyl)boron, Onyx tetra(pentafluorophenyl)borate, triphenylmethylonyx tetra(pentafluorophenyl)borate, benzene(diazoonium) tetra(pentafluorophenyl)borate, Onyx tetra(2,3,5,6-tetrafluorophenyl)borate, triphenylmethylonyx tetra(2,3,5,6-tetrafluorophenyl)borate, benzene(diazoonium) tetra(3,4,5-trifluorophenyl)borate, Onyx tetra(3,4,5-trifluorophenyl)borate, benzene(diazoonium) tetra(3,4,5-trifluorophenyl)borate, Onyx tetra(1,2,2-trifluorovinyl)borate, triphenylmethylonyx tetra(1,2,2-trifluorovinyl)borate, benzene(diazoonium) tetra(1,2,2-trifluorovinyl)borate, Ononium tetra(2,3,4,5-tetrafluorophenyl)borate, triphenylmethylononium tetra(2,3,4,5-tetrafluorophenyl)borate, and benzene(diazoonium)tetra(2,3,4,5-tetrafluorophenyl)borate. Easily available commercial ionic activators include N,N-dimethylphenylammonium tetra(pentafluorophenyl)borate and triphenylmethylononium tetra(pentafluorophenyl)borate.
[0090] Non-limiting examples of hindered phenols include butylated phenolic antioxidants, butylated hydroxytoluene, 2,6-di-tert-butyl-4-ethylphenol, 4,4'-methylenebis(2,6-di-tert-butylphenol), 1,3,5-dimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, and octadecyl-3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate.
[0091] To produce active metallocene-based catalyst systems, the amounts and molar ratios of the following three or four components are optimized: metallocene single-point catalyst, alkylaluminoxane, ion activator, and optionally hindered phenol.
[0092] In some embodiments, the unit-site catalyst used to prepare the first ethylene copolymer produces long-chain branches, and the first ethylene copolymer will contain long-chain branches, hereinafter referred to as "LCB".
[0093] LCB is a well-known structural phenomenon in ethylene copolymers and is well known to those skilled in the art. Traditionally, three methods exist for LCB analysis: nuclear magnetic resonance spectroscopy (NMR), e.g., see J. Crandall, J. Macromol. Sci., Rev. Macromol. Chem. Phys. 1989, 29, 201; triple-detection SEC equipped with a DRI, viscometer, and small-angle laser scattering detector, e.g., see WW. Yau and DR. Hill, Int. J. Polym. Anal. Charact. 1996; 2:151; and rheology, e.g., see WW. Graessley, Acc. Chem. Res. 1977, 10, 332-339. In embodiments of this disclosure, the long-chain branches are macromolecules in nature, i.e., long enough to be observed in NMR spectroscopy, triple-detector SEC experiments, or rheological experiments.
[0094] In some embodiments, the first ethylene copolymer contains long-chain branching characterized by the long-chain branching factor (LCBF) disclosed herein. In embodiments of this disclosure, the upper limit of the LCBF of the first ethylene copolymer may be 0.5000, 0.4000, 0.0375, or 0.3000 (dimensionless). In embodiments of this disclosure, the lower limit of the LCBF of the first ethylene copolymer may be 0.0010, 0.0015, 0.0020, 0.0050, 0.0070, 0.0100, 0.0500, or 0.1000 (dimensionless).
[0095] In embodiments of this disclosure, the LCBF of the first ethylene copolymer is at least 0.0010, or at least 0.0020, or at least 0.0050, or at least 0.0070, or at least 0.0100.
[0096] The first ethylene copolymer may contain catalyst residues that reflect the chemical composition of the catalyst formulation used to prepare it. Those skilled in the art will understand that catalyst residues are typically quantified by, for example, the parts per million (ppm) of metals in the first ethylene copolymer (or the polyethylene composition; see below), wherein the metals present originate from metals in the catalyst formulation used to prepare it. Non-limiting examples of metal residues that may be present include Group 4 metals titanium, zirconium, and hafnium. In embodiments of this disclosure, the upper limit of the ppm of metals in the first ethylene copolymer may be about 3.0 ppm, otherwise about 2.0 ppm, and still otherwise about 1.5 ppm. In embodiments of this disclosure, the lower limit of the ppm of metals in the first ethylene copolymer may be about 0.03 ppm, otherwise about 0.09 ppm, and still otherwise about 0.15 ppm.
[0097] In some embodiments, the first ethylene copolymer has 0.03-3.0 ppm of metal, or 0.09-3.0 ppm of metal, or 0.15-3.0 ppm of metal, or 0.03-2.0 ppm of metal, or 0.09-2.0 ppm of metal, or 0.15-2.0 ppm of metal, or 0.03-1.5 ppm of metal, or 0.09-1.5 ppm of metal, or 0.15-1.5 ppm of metal.
[0098] In some embodiments, the first ethylene copolymer has at least 1, or at least 2, or at least 3, or at least 4, or at least 5, or at least 7, or at least 8.5, or at least 10 short chain branches (SCB1) per thousand carbon atoms.
[0099] In some embodiments, the first ethylene copolymer has up to 100, or up to 75, or up to 50, or up to 30, or up to 25, or up to 20 short chain branches (SCB1) per thousand carbon atoms.
[0100] In some embodiments, the first ethylene copolymer has 1-100 short chain branches (SCB1) per thousand carbon atoms. In some embodiments, the first ethylene copolymer has 2-100 short chain branches (SCB1) per thousand carbon atoms, or 3-100 short chain branches (SCB1) per thousand carbon atoms, or 4-100 short chain branches (SCB1) per thousand carbon atoms, or 2-75 short chain branches (SCB1) per thousand carbon atoms, or 3-75 short chain branches (SCB1) per thousand carbon atoms, or 4-75 short chain branches (SCB1) per thousand carbon atoms, or 2-50 short chain branches (SCB1) per thousand carbon atoms. 1 short chain branch (SCB1), or 3-50 short chain branches per thousand carbon atoms (SCB1), or 4-50 short chain branches per thousand carbon atoms (SCB1), or 2-30 short chain branches per thousand carbon atoms (SCB1), or 3-30 short chain branches per thousand carbon atoms (SCB1), or 4-30 short chain branches per thousand carbon atoms (SCB1), or 5-30 short chain branches per thousand carbon atoms (SCB1), or 7-30 short chain branches per thousand carbon atoms (SCB1). SCB1), or having 2-25 short chain branches per thousand carbon atoms (SCB1), or having 3-25 short chain branches per thousand carbon atoms (SCB1), or having 4-25 short chain branches per thousand carbon atoms (SCB1), or having 5-25 short chain branches per thousand carbon atoms (SCB1), or having 7-25 short chain branches per thousand carbon atoms (SCB1), or having 8.5-25 short chain branches per thousand carbon atoms (SCB1), or having 10-25 short chain branches per thousand carbon atoms (SCB1). 1) It may have 2-20 short chain branches per thousand carbon atoms (SCB1), or 3-20 short chain branches per thousand carbon atoms (SCB1), or 4-20 short chain branches per thousand carbon atoms (SCB1), or 5-20 short chain branches per thousand carbon atoms (SCB1), or 7-20 short chain branches per thousand carbon atoms (SCB1), or 8.5-20 short chain branches per thousand carbon atoms (SCB1), or 10-20 short chain branches per thousand carbon atoms (SCB1).
[0101] In some implementations, the first ethylene copolymer has 2-30 short chain branches per thousand carbon atoms.
[0102] In some implementations, the first ethylene copolymer has 4-25 short chain branches per thousand carbon atoms.
[0103] In some implementations, the first ethylene copolymer has 4-20 short chain branches per thousand carbon atoms.
[0104] Short-chain branching (i.e., short-chain branching per thousand skeletal carbon atoms, SCB1) is attributed to the branching of α-olefin comonomers in ethylene copolymers, and for example, will have two carbon atoms for 1-butene comonomers, or four carbon atoms for 1-hexene comonomers, or six carbon atoms for 1-octene comonomers, etc.
[0105] In embodiments of this disclosure, the number of short chain branches per thousand carbon atoms (SCB1) in the first ethylene copolymer is greater than the number of short chain branches per thousand carbon atoms (SCB2) in the second ethylene copolymer.
[0106] In some implementations, the density of the first copolymer is less than the density of the second ethylene copolymer.
[0107] The density of the first ethylene copolymer is 0.880-0.930 g / cm³. 3 (Including any narrower range within this range and any values encompassed by these ranges). For example, in some embodiments, the density of the first ethylene copolymer is 0.880-0.925 g / cm³. 3 Or 0.880-0.922 g / cm³ 3 Or 0.880-0.920 g / cm³ 3 Or 0.880-0.918 g / cm³ 3 Or 0.890-0.930 g / cm³ 3 Or 0.890-0.925 g / cm³ 3 Or 0.890-0.922 g / cm³ 3 Or 0.890-0.920 g / cm³ 3 Or 0.890-0.918 g / cm³ 3 Or 0.900-0.930 g / cm³ 3 Or 0.900-0.925 g / cm³ 3 Or 0.900-0.922 g / cm³ 3 Or 0.900-0.920 g / cm³ 3 Or 0.900-0.918 g / cm³ 3 Or 0.905-0.930 g / cm³ 3 Or 0.905-0.925 g / cm³ 3 Or 0.905-0.922 g / cm³ 3 Or 0.905-0.920 g / cm³3 Or 0.905-0.918 g / cm³ 3 Or 0.910-0.930 g / cm³ 3 Or 0.910-0.925 g / cm³ 3 Or 0.910-0.922 g / cm³ 3 Or 0.910-0.920 g / cm³ 3 Or 0.910-0.918 g / cm³ 3 .
[0108] In some embodiments, the density of the first ethylene copolymer is 0.880 to less than 0.925 g / cm³. 3 .
[0109] In some embodiments, the density of the first ethylene copolymer is 0.890-0.925 g / cm³. 3 .
[0110] In some embodiments, the density of the first ethylene copolymer is less than 0.920 g / cm³. 3 or less than 0.918 g / cm 3 .
[0111] In some embodiments, the density of the first ethylene copolymer is greater than 0.900 g / cm³. 3 or greater than 0.905 g / cm 3 .
[0112] In some embodiments, the melt index (I2) of the first ethylene copolymer is smaller than the melt index (I2) of the second ethylene copolymer.
[0113] In some embodiments, the melt index (I2) of the first ethylene copolymer is ≤ 10 g / 10 min, or ≤ 5.0 g / 10 min, or ≤ 2.5 g / 10 min, or ≤ 1.0 g / 10 min, or ≤ 0.7 g / 10 min, or ≤ 0.5 g / 10 min, or < 0.5 g / 10 min.
[0114] In some embodiments, the melt index (I2) of the first ethylene copolymer is at most 1.0 g / 10 min.
[0115] In some embodiments, the melt index (I2) of the first ethylene copolymer is 0.001-10.0 g / 10min (including any narrower range within this range and any value covered by these ranges). For example, in some embodiments, the melt index (I2) of the first ethylene copolymer may be 0.001-7.5 g / 10 min, or 0.001-5.0 g / 10 min, or 0.001-2.5 g / 10 min, or 0.001-1.0 g / 10 min, or 0.001-0.7 g / 10 min, or 0.001-0.5 g / 10 min, or 0.01-10.0 g / 10 min, or 0.01-7.5 g / 10 min, or 0.01-5.0 g / 10 min, or 0.01-2.5 g / 10 min, or 0.01-1.0 g / 10 min, or 0.01-0.7 g / 10 min, or 0.01-0.5 g / 10 min, or 0.05-10.0 g / 10 min, or 0.05-7.5 g / 10 min. g / 10min, or 0.05-5.0 g / 10min, or 0.05-2.5 g / 10min, or 0.05-1.0 g / 10min, or 0.05-0.7 g / 10min, or 0.05-0.5 g / 10min, or 0.05-less than 0.5 g / 10min.
[0116] In some embodiments, the melt index (I2) of the first ethylene copolymer is 0.001-0.7 g / 10min.
[0117] In some embodiments, the melt flow ratio (I) of the first ethylene copolymer 21 / I2) is less than 25, or less than 23, or less than 20.
[0118] The weight-average molecular weight (M) of the first ethylene copolymer w The weight-average molecular weight (M) of the first ethylene copolymer is 130,000-275,000 g / mol (inclusive of any narrower range within this range and any values covered by these ranges). For example, in some embodiments, the weight-average molecular weight (M) of the first ethylene copolymer is... w The values are 130,000-260,000 g / mol, or 130,000-250,000 g / mol, or 130,000-240,000 g / mol, or 140,000-260,000 g / mol, or 140,000-250,000 g / mol, or 140,000-240,000 g / mol.
[0119] In some embodiments, the weight-average molecular weight (M) of the first ethylene copolymer wThe concentration is at least 125,000 g / mol, or at least 130,000 g / mol, or at least 135,000 g / mol, or at least 140,000 g / mol, or at least 145,000 g / mol.
[0120] In some embodiments, the weight-average molecular weight (M) of the first ethylene copolymer w The values are up to 275,000 g / mol, or up to 265,000 g / mol, or up to 260,000 g / mol, or up to 255,000 g / mol, or up to 250,000 g / mol, or up to 245,000 g / mol, or up to 240,000 g / mol.
[0121] In some embodiments, the molecular weight distribution (M...) of the first ethylene copolymer... w / M n The upper limit is about 2.7, or about 2.5, or about 2.4, or about 2.3. In some embodiments, the molecular weight distribution (M...) of the first ethylene copolymer... w / M n The lower limit is approximately 1.7, or approximately 1.8, or approximately 1.9.
[0122] Molecular weight distribution of the first ethylene copolymer (M w / M n The molecular weight distribution (M) of the first ethylene copolymer is 1.7-2.7 (inclusive of any narrower range within this range and any values covered by these ranges). For example, in some embodiments, the molecular weight distribution (M) of the first ethylene copolymer is... w / M n The values are 1.8-2.7, 1.8-2.5, 1.8-2.4, 1.8-2.3, 1.9-2.7, 1.9-2.5, 1.9-2.4, or 1.9-2.3.
[0123] In some implementations, the CDBI of the first ethylene copolymer 50 The upper limit can be about 98% by weight, about 95% by weight in other cases, and still about 90% by weight in other cases. In some embodiments, the CDBI of the first ethylene copolymer 50 The lower limit can be about 70% by weight, about 75% by weight in other cases, and about 80% by weight in other cases.
[0124] In some embodiments, the preparation of the first ethylene copolymer utilizes solution-phase polymerization in a single reactor to produce a product having the following CDBI. 50The unit site catalyst of the ethylene copolymer: by weight, at least 65%, or at least 70%, or at least 75%, or at least 80%, or at least 85%.
[0125] In some embodiments, the first ethylene copolymer has the following CDBI 50 Ethylene copolymers: by weight, greater than about 60%, or greater than about 65%, or greater than about 70%, or greater than about 75%, or greater than about 80%, or greater than about 85%.
[0126] The weight percentage (wt%) of the first ethylene copolymer in the polyethylene composition (i.e., the weight percentage of the first ethylene copolymer based on the total weight of the first and second ethylene copolymers) is 10 wt% to 60 wt% (inclusive of any narrower range within this range and any value covered by these ranges). For example, in some embodiments, the weight percentage (wt%) of the first ethylene copolymer in the polyethylene copolymer composition is about 10 wt% to about 55 wt%, or about 10 wt% to about 50 wt%, or about 10 wt% to about 45 wt%, or about 10 wt% to about 40 wt%, or about 15 wt% to about 55 wt%, or about 15 wt% to about 50 wt%, or about 15 wt% to about 40 wt%, or about 15 wt% to about 35 wt%, or about 20 wt% to about 45 wt%, or about 20 wt% to about 40 wt%, or about 20 wt% to about 35 wt%, or about 25 wt% to about 50 wt%, or about 25 wt% to about 40 wt%, or about 25 wt% to about 35 wt%.
[0127] Second ethylene copolymer In some embodiments, a multi-site catalyst system is used to prepare the second ethylene copolymer. Non-limiting examples of multi-site catalyst systems include Ziegler-Natta catalysts and chromium catalysts, both of which are well known in the art.
[0128] In some embodiments, the α-olefin that can be copolymerized with ethylene to prepare the second ethylene copolymer is selected from 1-propylene, 1-butene, 1-pentene, 1-hexene, and 1-octene, and mixtures thereof.
[0129] In some implementations, the second ethylene copolymer is a heterogeneous branched ethylene copolymer.
[0130] In some implementations, the second ethylene copolymer is an ethylene / 1-octene copolymer.
[0131] In some implementations, the second ethylene copolymer is prepared using a Ziegler-Natta catalyst system.
[0132] Ziegler-Natta catalyst systems are well known to those skilled in the art. Ziegler-Natta catalysts can be in-line or batch-based. The term "in-line Ziegler-Natta catalyst system" refers to the continuous synthesis of a small amount of active Ziegler-Natta catalyst system and the immediate injection of this catalyst into at least one continuously operating reactor, wherein the catalyst polymerizes ethylene with one or more optional α-olefins to form an ethylene polymer. The terms "batch-based Ziegler-Natta catalyst system" or "batch-based Ziegler-Natta pre-catalyst" refer to the synthesis of a much larger quantity of catalyst or pre-catalyst in one or more mixing vessels, either outside or separate from the continuously operating solution polymerization process. Once prepared, the batch-based Ziegler-Natta catalyst system or batch-based Ziegler-Natta pre-catalyst is transferred to a catalyst storage tank. The term "pre-catalyst" refers to an inactive catalyst system (inactive relative to ethylene polymerization); the pre-catalyst is converted into an active catalyst by adding an alkylaluminum co-catalyst. When needed, the pre-catalyst is pumped from the storage tank to at least one continuously operating reactor, where the active catalyst polymerizes ethylene with one or more optional α-olefins to form an ethylene copolymer. The pre-catalyst can be converted into the active catalyst either in or outside the reactor or along the route to the reactor.
[0133] A wide variety of compounds can be used to synthesize active Ziegler-Natta catalyst systems. Various compounds that can be combined to produce active Ziegler-Natta catalyst systems are described below. Those skilled in the art will understand that the embodiments described in this disclosure are not limited to the specific compounds disclosed.
[0134] Activated Ziegler-Natta catalyst systems can be formed from magnesium compounds, chloride compounds, metal compounds, alkylaluminum co-catalysts, and alkylaluminum. As those skilled in the art will appreciate, Ziegler-Natta catalyst systems may contain additional components; non-limiting examples of additional components are electron donors, such as amines or ethers.
[0135] Non-limiting examples of active in-line (or batch) Ziegler-Natta catalyst systems can be prepared as follows. In a first step, a solution of a magnesium compound is reacted with a solution of a chloride compound to form a magnesium chloride support suspended in solution. Non-limiting examples of magnesium compounds include Mg(R) 1 )2; where R 1 The functional groups can be the same or different straight-chain hydrocarbon groups, branched hydrocarbon groups, or cyclic hydrocarbon groups containing 1-10 carbon atoms. Non-limiting examples of chloride compounds include R. 2 Cl; where R 2Representing a hydrogen atom, or a straight-chain hydrocarbon group, branched hydrocarbon group, or cyclic hydrocarbon group containing 1-10 carbon atoms. In the first step, the solution of the magnesium compound may also contain an aluminum alkyl group. Non-limiting examples of aluminum alkyl groups include Al(R... 3 )3, where R 3 The functional groups can be the same or different straight-chain hydrocarbon groups, branched hydrocarbon groups, or cyclic hydrocarbon groups containing 1-10 carbon atoms. In the second step, a solution of the metal compound is added to a solution of magnesium chloride, and the metal compound is supported on the magnesium chloride. Non-limiting examples of suitable metal compounds include M(X). n orMO(X) n ; where M represents a metal selected from Groups 4 to 8 of the periodic table, or a mixture of metals selected from Groups 4 to 8; O represents oxygen; X represents chlorine or bromine; and n is an integer from 3 to 6 satisfying the oxidation state of the metal. Other non-limiting examples of suitable metal compounds include alkyl compounds of Groups 4 to 8 metals, metal alkoxides (which can be prepared by reacting a metal alkyl compound with an alcohol), and mixed ligand metal compounds containing a mixture of halide ligands, alkyl compound ligands, and alkoxide ligands. In the third step, a solution of the alkylaluminum co-catalyst is added to the metal compound supported on magnesium chloride. Various alkylaluminum co-catalysts represented by the following formula are suitable: Al(R 4 ) p (OR 9 ) q (X) r Where R 4 The groups can be the same or different hydrocarbon groups having 1-10 carbon atoms; OR 9 The groups can be the same or different alkoxy or aryloxy groups, where R 9 It is a hydrocarbon group with 1-10 carbon atoms bonded to oxygen; X is chlorine or bromine; and (p+q+r)=3, with the constraint that p is greater than 0. Commonly used non-limiting examples of alkylaluminum cocatalysts include trimethylaluminum, triethylaluminum, tributylaluminum, dimethylmethoxide aluminum, diethylethoxide aluminum, dibutylbutoxide aluminum, dimethylaluminum chloride or dimethylaluminum bromide, diethylaluminum chloride or diethylaluminum bromide, dibutylaluminum chloride or dibutylaluminum bromide, and ethylaluminum dichloride or ethylaluminum dibromide.
[0136] The methods described in the above paragraphs can be performed in a variety of solvents to synthesize active online (or batch) Ziegler-Natta catalyst systems; non-limiting examples of solvents include linear or branched C5-C... 12 Alkanes or mixtures thereof.
[0137] In some embodiments, the short-chain branching in the second ethylene copolymer can be about 0.05 to about 10.0 short-chain branches per thousand carbon atoms (SCB2 / 1000C). In some embodiments, the short-chain branching in the second ethylene copolymer can be 0.05-7.5 branches per thousand carbon atoms, or 0.05-5.0 branches, or 0.05-3.0 branches, or 0.05-1.5 branches, or 0.05-1.0 branches, or 0.08-7.5 branches, or 0.08-5.0 branches, or 0.08-3.0 branches, or 0.08-1.5 branches, or 0.08-1.0 branches, or 0.10-7.5 branches, or 0.10-5.0 branches, or 0.10-3.0 branches, or 0.10-1.5 branches, or 0.10-1.0 branches (SCB2 / 1000C).
[0138] In some embodiments, the second ethylene copolymer has 0.05-3 short chain branches per thousand carbon atoms (SCB2 / 1000C).
[0139] Short-chain branching (i.e., short-chain branching per thousand skeletal carbon atoms, SCB2) is attributed to the branching of α-olefin comonomers in ethylene copolymers, and for example, will have two carbon atoms for 1-butene comonomers, or four carbon atoms for 1-hexene comonomers, or six carbon atoms for 1-octene comonomers, etc.
[0140] In embodiments of this disclosure, the number of short chain branches per thousand carbon atoms (SCB2) in the second ethylene copolymer is less than the number of short chain branches per thousand carbon atoms (SCB1) in the first ethylene copolymer.
[0141] In some embodiments, the density of the second copolymer is greater than the density of the first ethylene copolymer.
[0142] The density of the second ethylene copolymer is 0.940-0.975 g / cm³. 3 (Including any narrower range within this range and any values covered by these ranges). For example, in some embodiments, the density of the second ethylene copolymer is 0.940-0.970 g / cm³. 3 Or 0.940-0.965 g / cm³ 3 Or 0.945-0.975 g / cm³ 3 Or 0.945-0.970 g / cm³ 3 Or 0.945-0.965 g / cm³ 3 Or 0.950-0.975 g / cm³ 3 Or 0.950-0.970 g / cm³ 3Or 0.950-0.965 g / cm³ 3 Or 0.955-0.975 g / cm³ 3 Or 0.955-0.972 g / cm³ 3 Or 0.955-0.970 g / cm³ 3 Or 0.955-0.967 g / cm³ 3 Or 0.955-0.965 g / cm³ 3 .
[0143] In some embodiments, the melt index (I2) of the second ethylene copolymer is greater than that of the first ethylene copolymer.
[0144] In some embodiments, the melt index (I2) of the second ethylene copolymer is at least 2.0 g / 10 min.
[0145] In some embodiments, the melt index (I2) of the second ethylene copolymer is 2.0-500 g / 10min (including any narrower range within this range and any value covered by these ranges). For example, in some embodiments, the melt index (I2) of the second ethylene copolymer is 2-250 g / 10min, or 2-100 g / 10min, or 2-75 g / 10min, or 2-50 g / 10min, or 2-40 g / 10min, or 2-30 g / 10min, or 2-25 g / 10min, or 2-20 g / 10min, or 5-250 g / 10min, or 5-100 g / 10min, or 5-75 g / 10min, or 5-50 g / 10min, or 5-40 g / 10min, or 5-30 g / 10min, or 5-25 g / 10min, or 5-20 g / 10min, or 10-250 g / 10min, or 10-100 g / 10min, or 10-75 g / 10min, or 10-50 g / 10min. g / 10min, or 10-40 g / 10min, or 10-30 g / 10min, or 10-25 g / 10min, or 10-20 g / 10min.
[0146] In some embodiments, the melt index (I2) of the second ethylene copolymer is 2.0-50 g / 10min.
[0147] The weight-average molecular weight (M) of the second ethylene copolymer w The weight-average molecular weight (M) of the first ethylene copolymer is 20,000-90,000 g / mol (inclusive of any narrower range within this range and any values covered by these ranges). For example, in some embodiments, the weight-average molecular weight (M) of the first ethylene copolymer is...w The values are 20,000-80,000 g / mol, or 20,000-70,000 g / mol, or 20,000-65,000 g / mol, or 30,000-90,000 g / mol, or 30,000-80,000 g / mol, or 30,000-70,000 g / mol, or 30,000-65,000 g / mol, or 40,000-90,000 g / mol, or 40,000-80,000 g / mol, or 40,000-70,000 g / mol, or 40,000-65,000 g / mol.
[0148] In some embodiments, the weight-average molecular weight (M) of the second ethylene copolymer w The concentration is at least 20,000 g / mol, or at least 30,000 g / mol, or at least 40,000 g / mol.
[0149] In some embodiments, the weight-average molecular weight (M) of the second ethylene copolymer w The values are up to 90,000 g / mol, or up to 80,000 g / mol, or up to 70,000 g / mol, or up to 65,000 g / mol.
[0150] The weight-average molecular weight (M) of the second ethylene copolymer w The weight-average molecular weight (M) of the first ethylene copolymer is lower than that of the first ethylene copolymer. w ).
[0151] In some embodiments, the molecular weight distribution (M...) of the second ethylene copolymer... w / M n The upper limit of ) is about 4.0, or about 3.5, or about 3.3, or about 3.1, or about 2.9, or about 2.8, or about 2.7. In some embodiments, the molecular weight distribution (M) of the second ethylene copolymer is... w / M n The lower limit is approximately 2.0, or approximately 2.2, or approximately 2.4, or approximately 2.5.
[0152] In the implementation scheme, the molecular weight distribution (M) of the second ethylene copolymer w / M n The molecular weight distribution (M) of the second ethylene copolymer is 2.0-4.5 (inclusive of any narrower range within this range and any values covered by these ranges). For example, in some embodiments, the molecular weight distribution (M) of the second ethylene copolymer is... w / M nThe values are 2.0-4.0, 2.0-3.5, 2.0-3.1, 2.0-2.9, 2.0-2.8, 2.0-2.7, 2.2-3.3, 2.2-3.1, 2.2-2.9, 2.2-2.8, 2.2-2.7, 2.4-3.3, 2.4-3.1, 2.4-2.9, 2.4-2.8, 2.4-2.7, 2.5-3.3, 2.5-3.1, 2.5-2.9, 2.5-2.8, or 2.5-2.7.
[0153] In some embodiments, CDBI is generated during solution-phase polymerization in a single reactor during the preparation of the second ethylene copolymer. 50 Multisite catalysts of ethylene copolymers less than 60 wt% or less than 50 wt%.
[0154] The weight percentage (wt%) of the second ethylene copolymer in the polyethylene composition (i.e., the weight percentage of the second ethylene copolymer based on the total weight of the first and second ethylene copolymers) is 90 wt% to 40 wt% (inclusive of any narrower range within this range and any value covered by these ranges). For example, in some embodiments, the weight percentage (wt%) of the second ethylene copolymer in the polyethylene copolymer composition is about 90 wt% to about 45 wt%, or about 90 wt% to about 50 wt%, or about 90 wt% to about 55 wt%, or about 90 wt% to about 60 wt%, or about 85 wt% to about 45 wt%, or about 85 wt% to about 50 wt%, or about 85 wt% to about 60 wt%, or about 85 wt% to about 65 wt%, or about 80 wt% to about 55 wt%, or about 80 wt% to about 60 wt%, or about 80 wt% to about 65 wt%, or about 75 wt% to about 50 wt%, or about 75 wt% to about 60 wt%, or about 75 wt% to about 65 wt%.
[0155] Polyethylene composition The polyethylene composition comprises a first ethylene copolymer and a second ethylene copolymer, each as defined above.
[0156] The polyethylene compositions disclosed herein can be prepared using any techniques well known in the art, including but not limited to melt blending, solution blending, or in-reactor blending for combining a first ethylene copolymer and a second ethylene copolymer.
[0157] In some embodiments, the polyethylene compositions of this disclosure are prepared as follows: a single-site catalyst is used in a first reactor to produce a first ethylene copolymer, and a multi-site catalyst is used in a second reactor to produce a second ethylene copolymer.
[0158] In some embodiments, the polyethylene compositions of this disclosure are prepared by: polymerizing ethylene with α-olefins in a first reactor using a single-site catalyst to form a first ethylene copolymer; and polymerizing ethylene with α-olefins in a second reactor using a multi-site catalyst to form a second ethylene copolymer.
[0159] In some embodiments, the polyethylene compositions of this disclosure are prepared by: polymerizing ethylene with α-olefins in a first solution-phase polymerization reactor using a single-site catalyst to form a first ethylene copolymer; and polymerizing ethylene with α-olefins in a second solution-phase polymerization reactor using a multi-site catalyst to form a second ethylene copolymer.
[0160] In some embodiments, the polyethylene composition of the present disclosure is prepared by: polymerizing ethylene with α-olefins in a first solution-phase polymerization reactor using a single-site catalyst to form a first ethylene copolymer; and polymerizing ethylene with α-olefins in a second solution-phase polymerization reactor using a multi-site catalyst to form a second ethylene copolymer, wherein the first solution-phase polymerization reactor and the second solution-phase polymerization reactor are arranged in series with each other.
[0161] In some embodiments, the polyethylene composition of the present disclosure is prepared by: polymerizing ethylene with α-olefins in a first solution-phase polymerization reactor using a single-site catalyst to form a first ethylene copolymer; and polymerizing ethylene with α-olefins in a second solution-phase polymerization reactor using a multi-site catalyst to form a second ethylene copolymer, wherein the first solution-phase polymerization reactor and the second solution-phase polymerization reactor are arranged in parallel with each other.
[0162] In some implementations, the solution-phase polymerization reactor used as the first solution-phase reactor is a continuous stirred tank reactor or a tubular reactor.
[0163] In some implementations, the solution-phase polymerization reactor used as the second solution-phase reactor is a continuous stirred tank reactor or a tubular reactor.
[0164] In solution polymerization, the monomer is dissolved / dispersed in a solvent before being fed into the reactor, or, for gaseous monomers, fed into the reactor so that it dissolves in the reaction mixture. Prior to mixing, the solvent and monomer are typically purified to remove potential catalyst poisons, such as water, oxygen, or metallic impurities. Feedstock purification follows standard practices in the art, such as the use of molecular sieves, alumina beds, and oxygen-scavenging catalysts for monomer purification. Preferably, the solvent itself (e.g., methylpentane, cyclohexane, hexane, or toluene) is also treated in a similar manner.
[0165] The raw materials can be heated or cooled before being fed into the reactor.
[0166] Typically, catalyst components can be premixed in the solvent used for the reaction or fed into the reactor as a separate stream. In some cases, premixing the catalyst components can provide them with reaction time before they enter the polymerization reaction zone. Such "on-line mixing" techniques are well known to those skilled in the art.
[0167] Solution polymerization methods for the polymerization or copolymerization of ethylene are well known in the art (see, for example, U.S. Patents 6,372,864 and 6,777,509). These methods are carried out in the presence of an inert hydrocarbon solvent. Various solvents can be used as process solvents in the solution-phase polymerization reactor; non-limiting examples include linear, branched, or cyclic C5-C solvents. 12 Alkanes. Suitable catalyst component solvents include aliphatic and aromatic hydrocarbons. Non-limiting examples of aliphatic catalyst component solvents include linear, branched, or cyclic C4 hydrocarbons. 5-12 Aliphatic hydrocarbons, such as pentane, methylpentane, hexane, heptane, octane, cyclohexane, cyclopentane, methylcyclohexane, hydrogenated naphtha, or combinations thereof. Non-limiting examples of solvents for aromatic catalyst components include benzene, toluene (methylbenzene), ethylbenzene, o-xylene (1,2-dimethylbenzene), m-xylene (1,3-dimethylbenzene), p-xylene (1,4-dimethylbenzene), mixtures of xylene isomers, trimethylbenzene (1,2,3-trimethylbenzene), pseudotrimethylbenzene (1,2,4-trimethylbenzene), mesitylene (1,3,5-trimethylbenzene), mixtures of trimethylbenzene isomers, tetramethylbenzene (1,2,3,4-tetramethylbenzene), dulene (1,2,3,5-tetramethylbenzene), mixtures of tetramethylbenzene isomers, pentamethylbenzene, hexamethylbenzene, and combinations thereof.
[0168] Polymerization temperatures in conventional solution processes can range from about 80°C to about 300°C. In some embodiments, the polymerization temperature in solution processes is about 120°C to about 250°C. Polymerization pressures in solution processes can be "medium-pressure processes," meaning the pressure in the reactor is less than about 6,000 psi (about 42,000 kPa). In some embodiments, polymerization pressures in solution processes can be about 10,000 to about 40,000 kPa, or about 14,000 to about 22,000 kPa (i.e., about 2,000 psi to about 3,000 psi).
[0169] Suitable comonomers (i.e., α-olefins) for copolymerization with ethylene in solution-phase polymerization methods include C 3-20 Monoolefins and dienes. In some embodiments, the comonomers that can be copolymerized with ethylene include unsubstituted or disubstituted monomers with at most two C atoms. 1-6 Alkyl-substituted C 3-12 α-olefins, unsubstituted or with at most two components selected from C10. 1-4 Alkyl substituents substituted C 8-12 Vinyl aromatic monomers, unsubstituted or C 1-4 Alkyl-substituted C 4-12 Linear or cyclic dienes. In a further embodiment, the α-olefin that can be copolymerized with ethylene is one or more of the following: propylene, 1-butene, 1-pentene, 1-hexene, 1-octene and 1-decene, styrene, α-methylstyrene; and ring-restricted cyclic olefins, such as cyclobutene, cyclopentene, dicyclopentadiene, norbornene, alkyl-substituted norbornene, alkenyl-substituted norbornene, etc. (e.g., 5-methylene-2-norbornene and 5-ethylidene-2-norbornene, bicyclo-(2,2,1)-hept-2,5-diene).
[0170] In some embodiments, the polyethylene composition comprises ethylene and one or more α-olefins selected from the group consisting of 1-butene, 1-hexene, 1-octene, and mixtures thereof.
[0171] In some embodiments, the polyethylene composition comprises ethylene and one or more α-olefins selected from the group consisting of 1-hexene, 1-octene, and mixtures thereof.
[0172] In some embodiments, the polyethylene composition comprises ethylene and 1-octene.
[0173] In some embodiments, the polyethylene composition has 0.1-7.5 mol% (inclusive of any narrower range within this range and any values covered by these ranges) of one or more α-olefins. For example, in some embodiments, the polyethylene composition has 0.1-5.0 mol% of one or more α-olefins, or 0.1-3.0 mol% of one or more α-olefins, or 0.5-5.0 mol% of one or more α-olefins, or 0.5-3 mol% of one or more α-olefins, or 0.1-2.5 mol% of one or more α-olefins, or 0.1-2.0 mol% of one or more α-olefins, or 0.5-2.0 mol% of one or more α-olefins.
[0174] In some embodiments, the polyethylene composition contains 0.1-5.0 mol% of 1-octene, or 0.1-3.0 mol% of 1-octene, or 0.5-5.0 mol% of 1-octene, or 0.5-3 mol% of 1-octene, or 0.1-2.5 mol% of 1-octene, or 0.1-2.0 mol% of 1-octene, or 0.5-2.0 mol% of 1-octene.
[0175] The ratio (SCB1 / SCB2) of the number of short-chain branches per thousand carbon atoms in the first ethylene copolymer (i.e., SCB1) to the number of short-chain branches per thousand carbon atoms in the second ethylene copolymer (i.e., SCB2) in the second ethylene copolymer is at least 5.0 (i.e., SCB1 / SCB2 ≥ 5.0). In some embodiments, the ratio of short-chain branching (SCB1) in the first ethylene copolymer to short-chain branching (SCB2) in the second ethylene copolymer is at least 7.5 or greater than 7.5. In some embodiments, the ratio of short-chain branching (SCB1) in the first ethylene copolymer to short-chain branching (SCB2) in the second ethylene copolymer is at least 10.0 or greater than 10.0. In some embodiments, the ratio of short-chain branching (SCB1) in the first ethylene copolymer to short-chain branching (SCB2) in the second ethylene copolymer is at least 12.5 or greater than 12.5. In some embodiments, the ratio of short-chain branching (SCB1) in the first ethylene copolymer to short-chain branching (SCB2) in the second ethylene copolymer is at least 15.0 or greater than 15.0.
[0176] In some embodiments, the ratio of the number of short chain branches per thousand carbon atoms in the first ethylene copolymer to the number of short chain branches per thousand carbon atoms in the second ethylene copolymer (SCB1 / SCB2) is at least 10.
[0177] In one embodiment of this disclosure, the ratio (SCB1 / SCB2) of the number of short chain branches per thousand carbon atoms in the first ethylene copolymer (i.e., SCB1) to the number of short chain branches per thousand carbon atoms in the second ethylene copolymer (i.e., SCB2) in the second ethylene copolymer is 5.0-100, or 5.0-80.0, or 10.0-100.0, or 10.0-80.0.
[0178] In some embodiments, the polyethylene composition is composed of M z Short chain branching frequency (SCB-M) z M w Short chain branching frequency (SCB-M) w ) and M n Short chain branching frequency (SCB-M) n Characterization, where the short-chain branching frequency is determined in GPC-FTIR analysis, specifically in M... z M w and M n The number of short-chain branches per thousand polymer backbone carbons.
[0179] In some embodiments, the short-chain branching content of the polyethylene composition satisfies the following formula: SCB-M z >SCB-M w >SCB-M n .
[0180] In some embodiments, the SCB-M of the polyethylene composition z The SCB-M of the polyethylene composition has more than 2.0 short chain branches per thousand polymer backbone carbons. In some embodiments, the SCB-M of the polyethylene composition... z For every thousand polymer backbone carbons, there are 2.0-7.5 short chain branches.
[0181] In some embodiments, the SCB-M of the polyethylene composition w The SCB-M of the polyethylene composition is 0.5-5.0 short chain branches per thousand polymer backbone carbons. In some embodiments, the SCB-M of the polyethylene composition is... w For every thousand polymer backbone carbons, there are 0.5-3.5 short chain branches.
[0182] In some embodiments, the SCB-M of the polyethylene composition n The number of short chain branches is less than 2.0 per thousand polymer backbone carbons, or less than 1.0 per thousand polymer backbone carbons.
[0183] In some embodiments, the density of the polyethylene composition is ≥ 0.940 g / cm³. 3or >0.940 g / cm 3 or ≥ 0.942 g / cm³ 3 or >0.942 g / cm 3 or ≥ 0.944 g / cm³ 3 or >0.944 g / cm 3 or ≥ 0.945 g / cm³ 3 or >0.945 g / cm 3 or ≥ 0.946 g / cm³ 3 or > 0.946 g / cm³ 3 or ≥ 0.947 g / cm³ 3 or >0.947 g / cm 3 .
[0184] In some embodiments, the density of the polyethylene composition is > 0.942 g / cm³. 3 In some embodiments, the density of the polyethylene composition is > 0.947 g / cm³. 3 .
[0185] In some embodiments, the density of the polyethylene composition is 0.940-0.965 g / cm³. 3 (Including any narrower range within this range and any values encompassed by these ranges). For example, in some embodiments, the density of the polyethylene composition is 0.940-0.960 g / cm³. 3 Or 0.940-0.957 g / cm³ 3 Or 0.940-0.955 g / cm³ 3 Or 0.940-0.953 g / cm³ 3 Or 0.940-0.950 g / cm³ 3 Or 0.942-0.960 g / cm³ 3 Or 0.942-0.957 g / cm³ 3 Or 0.942-0.955 g / cm³ 3 Or 0.942-0.953 g / cm³ 3 Or 0.942-0.950 g / cm³ 3 Or 0.944-0.960 g / cm³ 3 Or 0.944-0.957 g / cm³ 3 Or 0.944-0.955 g / cm³ 3 Or 0.944-0.953 g / cm³ 3 Or 0.944-0.950 g / cm³ 3Or 0.945-0.960 g / cm³ 3 Or 0.945-0.957 g / cm³ 3 Or 0.945-0.955 g / cm³ 3 Or 0.945-0.953 g / cm³ 3 Or 0.945-0.950 g / cm³ 3 Or 0.946-0.960 g / cm³ 3 Or 0.946-0.957 g / cm³ 3 Or 0.946-0.955 g / cm³ 3 Or 0.946-0.953 g / cm³ 3 Or 0.946-0.950 g / cm³ 3 Or 0.947-0.960 g / cm³ 3 Or 0.947-0.957 g / cm³ 3 Or 0.947-0.955 g / cm³ 3 Or 0.947-0.953 g / cm³ 3 Or 0.947-0.950 g / cm³ 3 .
[0186] In some embodiments, the density of the polyethylene composition is 0.942-0.957 g / cm³. 3 .
[0187] In some embodiments, the density of the polyethylene composition is 0.945-0.955 g / cm³. 3 .
[0188] In some embodiments, the density of the polyethylene composition is 0.947-0.955 g / cm³. 3 .
[0189] In some embodiments, the weight-average molecular weight (M) of the polyethylene composition is... w The values are ≤ 130,000 g / mol, or ≤ 120,000 g / mol, or ≤ 110,000 g / mol, or ≤ 105,000 g / mol, or < 130,000 g / mol, or < 120,000 g / mol, or < 110,000 g / mol, or < 105,000 g / mol.
[0190] In some embodiments, the weight-average molecular weight (M) of the polyethylene composition is... wThe weight-average molecular weight (M) of the polyethylene composition is 30,000-150,000 g / mol (inclusive of any narrower range within this range and any values covered by these ranges). For example, in some embodiments, the weight-average molecular weight (M) of the polyethylene composition is... w The values are 50,000-150,000 g / mol, or 50,000-130,000 g / mol, or 50,000-120,000 g / mol, or 70,000-150,000 g / mol, or 70,000-130,000 g / mol, or 70,000-120,000 g / mol, or 70,000-110,000 g / mol, or 70,000-105,000 g / mol, or 75,000-130,000 g / mol, or 75,000-120,000 g / mol, or 75,000-110,000 g / mol, or 75,000-105,000 g / mol.
[0191] In some embodiments, the weight-average molecular weight (M) of the polyethylene composition is... w The concentration is 70,000-120,000 g / mol.
[0192] In some embodiments, the number-average molecular weight (M) of the polyethylene composition is... n The values are ≤ 60,000 g / mol, or ≤ 50,000 g / mol, or < 50,000 g / mol, or ≤ 45,000 g / mol, or < 45,000 g / mol, or ≤ 40,000 g / mol, or < 40,000 g / mol, or ≤ 35,000 g / mol, or < 35,000 g / mol.
[0193] In some embodiments, the number-average molecular weight (M) of the polyethylene composition is... n The number-average molecular weight (Mn) of the polyethylene composition is 5,000-60,000 g / mol (inclusive of any narrower range within this range and any values covered by these ranges). For example, in some embodiments, the number-average molecular weight (Mn) of the polyethylene composition is... nThe values are 5,000-50,000 g / mol, or 10,000-50,000 g / mol, or 10,000-45,000 g / mol, or 15,000-45,000 g / mol, or 20,000-45,000 g / mol, or 10,000-40,000 g / mol, or 15,000-40,000 g / mol, or 20,000-35,000 g / mol, or 15,000-35,000 g / mol, or 20,000-35,000 g / mol.
[0194] In some embodiments, the number-average molecular weight (M) of the polyethylene composition is... n The concentration is 20,000-40,000 g / mol.
[0195] In some embodiments, the Z-average molecular weight (M) of the polyethylene composition is... z The values are ≤ 400,000 g / mol, or ≤ 350,000 g / mol, or ≤ 310,000 g / mol, or ≤ 275,000 g / mol, or ≤ 250,000 g / mol, or < 400,000 g / mol, or < 350,000 g / mol, or < 310,000 g / mol, or < 275,000 g / mol, or < 250,000 g / mol.
[0196] In some embodiments, the Z-average molecular weight (M) of the polyethylene composition is... z The Z-average molecular weight (M) of the polyethylene composition is <400,000 g / mol. In some embodiments, the Z-average molecular weight (M) of the polyethylene composition is <400,000 g / mol. z The value is <310,000 g / mol.
[0197] In some embodiments, the Z-average molecular weight (M) of the polyethylene composition is... z The Z-average molecular weight (M) of the polyethylene composition is 100,000-400,000 g / mol (inclusive of any narrower range within this range and any values covered by these ranges). For example, in some embodiments, the Z-average molecular weight (M) of the polyethylene composition is... zThe values are 100,000-350,000 g / mol, or 125,000-350,000 g / mol, or 150,000-350,000 g / mol, or 160,000-350,000 g / mol, or 200,000-350,000 g / mol, or 100,000-310,000 g / mol, or 125,000-310,000 g / mol, or 150,000-310,000 g / mol, or 160,000-310,000 g / mol, or 200,000-310,000 g / mol, or 100,000-275,000 g / mol, or 125,000-275,000 g / mol. g / mol, or 150,000-275,000 g / mol, or 160,000-275,000 g / mol, or 200,000-275,000 g / mol, or 100,000-250,000 g / mol, or 125,000-250,000 g / mol, or 150,000-250,000 g / mol, or 160,000-250,000 g / mol.
[0198] In some embodiments, the Z-average molecular weight (M) of the polyethylene composition is... z The value is 100,000-350,000 g / mol.
[0199] In some embodiments, the Z-average molecular weight (M) of the polyethylene composition is... z The value is 100,000-250,000 g / mol.
[0200] In some embodiments, the polyethylene composition exhibits a bimodal distribution (i.e., a bimodal molecular weight distribution) in gel permeation chromatography (GPC) analysis.
[0201] In some embodiments, the polyethylene copolymer composition exhibits a bimodal distribution in gel permeation chromatography produced according to the method of ASTM D6474-99.
[0202] In some embodiments, the polyethylene composition exhibits a unimodal distribution (i.e., a unimodal molecular weight distribution) in gel permeation chromatography (GPC) analysis.
[0203] In some embodiments, the polyethylene copolymer composition exhibits a unimodal distribution in gel permeation chromatography produced according to the method of ASTM D6474-99.
[0204] The term "unimodal" is defined herein as indicating that only one significant peak or obvious maximum value will exist in the GPC curve. In contrast, the term "bimodal" is intended to indicate that in addition to the first peak, there will be a secondary peak or shoulder peak, representing a higher or lower molecular weight component (i.e., the molecular weight distribution may allegedly have two maximum values in the molecular weight distribution curve). Alternatively, the term "bimodal" means that there are two maximum values in the molecular weight distribution curve generated according to the method of ASTM D6474-99. The term "multimodal" indicates that there are two or more (usually more than two) maximum values in the molecular weight distribution curve generated according to the method of ASTM D6474-99.
[0205] In some embodiments, the molecular weight distribution (M) of the polyethylene composition is... w / M n The molecular weight distribution (M) of the polyethylene composition is ≤ 6.0, or < 6.0, or ≤ 5.5, or < 5.5, or ≤ 5.0, or < 5.0, or ≤ 4.5, or < 4.5, or ≤ 4.0, or < 4.0, or ≤ 3.5, or < 3.5, or ≤ 3.0, or < 3.0. In some embodiments, the molecular weight distribution (M) of the polyethylene composition is... w / M n The molecular weight distribution (M) of the polyethylene composition is 2.0-6.5 (inclusive of any narrower range within this range and any values covered by these ranges). For example, in some embodiments, the molecular weight distribution (M) of the polyethylene composition is... w / M n The values are 2.0-6.0, 2.0-5.5, 2.0-5.0, 2.0-4.5, 2.0-4.0, 2.0-3.5, 2.3-6.0, 2.3-5.5, 2.3-5.0, 2.3-4.5, 2.3-4.0, or 2.3-3.5.
[0206] In some embodiments, the molecular weight distribution (M) of the polyethylene composition is... w / M n The molecular weight distribution (M) of the polyethylene composition is less than 4.5. In some embodiments, the molecular weight distribution (M) of the polyethylene composition is... w / M n The value is 2.0-4.0.
[0207] In some embodiments, the melt index (I2) of the polyethylene composition is at most 3.0 g / 10 min, or at most 2.8 g / 10 min, or at most 2.6 g / 10 min, or at most 2.4 g / 10 min, or at most 2.2 g / 10 min, or at most 2.0 g / 10 min, or at most 1.8 g / 10 min, or less than 3.0 g / 10 min, or less than 2.8 g / 10 min, or less than 2.6 g / 10 min, or less than 2.4 g / 10 min, or less than 2.2 g / 10 min, or less than 2.0 g / 10 min, or less than 1.8 g / 10 min.
[0208] In the embodiments, the melt index (I2) of the polyethylene composition is 1.0-3.0 g / 10min, or 1.0-less than 3.0 g / 10min, or less than 3.0 g / 10min (including any narrower range within these ranges and any value covered by these ranges). For example, in some embodiments, the melt index (I2) of the polyethylene composition is 1.0-2.8 g / 10 min, or 1.0-2.6 g / 10 min, or 1.0-2.4 g / 10 min, or 1.0-2.2 g / 10 min, or 1.0-2.0 g / 10 min, or 1.0-1.8 g / 10 min, or 1.3-3.0 g / 10 min, or 1.3-2.8 g / 10 min, or 1.3-2.6 g / 10 min, or 1.3-2.4 g / 10 min, or 1.3-2.2 g / 10 min, or 1.3-2.0 g / 10 min, or 1.3-1.8 g / 10 min, or 1.5-3.0 g / 10 min, or 1.5-2.8 g / 10 min, or 1.5-2.6 g / 10 min. g / 10min, or 1.5-2.4 g / 10min, or 1.5-2.2 g / 10min, or 1.5-2.0 g / 10min, or 1.5-1.8 g / 10min.
[0209] In some embodiments, the melt index (I2) of the polyethylene composition is 1.3-3.0 g / 10min.
[0210] In some embodiments, the melt index (I2) of the polyethylene composition is 1.3 to less than 3.0 g / 10min.
[0211] In some embodiments, the melt index (I2) of the polyethylene composition is 1.5-3.0 g / 10min.
[0212] In some embodiments, the melt index (I2) of the polyethylene composition is 1.5 to less than 3.0 g / 10min.
[0213] In some embodiments, the melt index (I2) of the polyethylene composition is 1.3-2.6 g / 10min.
[0214] In some embodiments, the high melt index (I) of the polyethylene composition 21 The values are at least 20 g / 10 min, or at least 25 g / 10 min, or at least 30 g / 10 min, or at least 35 g / 10 min, or at least 40 g / 10 min, or greater than 20 g / 10 min, or at least 25 g / 10 min, or at least 30 g / 10 min, or at least 35 g / 10 min, or at least 40 g / 10 min.
[0215] In some embodiments, the high melt index (I) of the polyethylene composition 21 The concentration should be at least 30 g / 10 min.
[0216] In some embodiments, the high melt index (I) of the polyethylene composition 21 The melt index is 20-150 g / 10min (inclusive of any narrower range and any value covered by these ranges). For example, in some embodiments, the high-load melt index (I0) of the polyethylene composition... 21 The values are 20-125 g / 10min, or 20-100 g / 10min, or 20-80 g / 10min, or 20-70 g / 10min, or 20-60 g / 10min, or 25-150 g / 10min, or 25-125 g / 10min, or 25-100 g / 10min, or 25-80 g / 10min, or 25-70 g / 10min, or 25-60 g / 10min, or 30-150 g / 10min, or 30-125 g / 10min, or 30-100 g / 10min, or 30-80 g / 10min, or 30-70 g / 10min, or 30-60 g / 10min, or 35-150 g / 10min, or 35-125 g / 10min. g / 10min, or 35-100 g / 10min, or 35-80 g / 10min, or 35-70 g / 10min, or 35-60 g / 10min, or 40-150 g / 10min, or 40-125 g / 10min, or 40-100 g / 10min, or 40-80 g / 10min, or 40-70 g / 10min, or 40-60 g / 10min.
[0217] In some embodiments, the high melt index (I) of the polyethylene composition21 The concentration is 30-100 g / 10min.
[0218] In some embodiments, the melt flow ratio (I) of the polyethylene composition 21 / I2) is ≤ 60, or < 60, or ≤ 50, or < 50, or ≤ 40, or < 40. In some embodiments, the melt flow ratio (I) of the polyethylene composition is... 21 / I2) is 15-60 (inclusive of any narrower range within this range and any values covered by these ranges). For example, in some embodiments, the melt flow ratio (I / I2) of the polyethylene composition is... 21 / I2) is 15-50, or 15-40, or 20-60, or 20-50, or 20-40, or 25-60, or 25-50, or 25-40.
[0219] In some embodiments, the melt flow ratio (I) of the polyethylene composition 21 / I2) is 20-50.
[0220] In some embodiments, such as those measured using GPC-FTIR, the polyethylene composition will have a reverse or partially reverse comonomer distribution profile. If measured using GPC-FTIR, the distribution is described as “normal” if comonomer incorporation decreases with molecular weight. If measured using GPC-FTIR, the comonomer distribution is described as “flat” or “uniform” if comonomer incorporation is approximately constant with molecular weight. The terms “reverse comonomer distribution” and “partially reverse comonomer distribution” indicate that in the GPC-FTIR data obtained for the copolymer, there are one or more higher molecular weight fractions with higher comonomer incorporation than one or more lower molecular weight fractions. The term “reverse (or reverse) comonomer distribution” is used herein to indicate that the comonomer content of various polymer fractions is not substantially uniform across the entire molecular weight range of the ethylene copolymer, and that the higher molecular weight fractions have proportionally higher comonomer contents (i.e., the distribution is described as “reverse” or “reverse” if comonomer incorporation increases with molecular weight). When the comonomer incorporation increases and then decreases with increasing molecular weight, the comonomer distribution is still considered "reverse," but it can also be described as "partially reversed." A partially reversed comonomer distribution will exhibit a peak or maximum value.
[0221] In some embodiments, such as those measured using GPC-FTIR, the polyethylene composition has a reverse comonomer distribution profile.
[0222] In some embodiments, such as those measured using GPC-FTIR, the polyethylene composition has a partially reverse comonomer distribution profile.
[0223] In some embodiments, the CDBI of the polyethylene composition 50 It is approximately 20-75% by weight, or approximately 20-65% by weight, or approximately 20-60% by weight.
[0224] In some embodiments, the upper limit of the hafnium content (ppm) in the polyethylene composition by weight is about 3.0 ppm, or about 2.5 ppm, or about 2.4 ppm, or about 2.0 ppm, or about 1.5 ppm, or about 1.0 ppm, or about 0.75 ppm, or about 0.5 ppm. In some embodiments, the lower limit of the hafnium content (ppm) in the polyethylene composition is about 0.0015 ppm, or about 0.0050 ppm, or about 0.0075 ppm, or about 0.010 ppm, or about 0.015 ppm, or about 0.030 ppm, or about 0.050 ppm, or about 0.075 ppm, or about 0.100 ppm, or about 0.150 ppm, or about 0.175 ppm, or about 0.200 ppm.
[0225] In some embodiments, the polyethylene composition has at least 0.0015 ppm of hafnium, or at least 0.005 ppm of hafnium, or at least 0.0075 ppm of hafnium, or at least 0.015 ppm of hafnium, or at least 0.030 ppm of hafnium, or at least 0.050 ppm of hafnium, or at least 0.075 ppm of hafnium, or at least 0.100 ppm of hafnium, or at least 0.125 ppm of hafnium, or at least 0.150 ppm of hafnium, or at least 0.175 ppm of hafnium, or at least 0.200 ppm of hafnium, or at least 0.300 ppm of hafnium, or at least 0.350 ppm of hafnium.
[0226] In some embodiments, the polyethylene composition has 0.0015-2.4 ppm hafnium, or 0.0050-2.4 ppm hafnium, or 0.0075-2.4 ppm hafnium, or 0.010-2.4 ppm hafnium, or 0.015-2.4 ppm hafnium, or 0.050-3.0 ppm hafnium, or 0.050-2.4 ppm hafnium, or 0.075-2.4 ppm hafnium, or 0.075-2.0 ppm hafnium, or 0.075-1.5 ppm hafnium, or 0.075-1.0 ppm hafnium, or 0.075-0.75 ppm hafnium, or 0.100-2.0 ppm hafnium, or 0.100-1.5 ppm hafnium. Hafnium in ppm, or 0.100-1.0 ppm, or 0.100-0.75 ppm, or 0.20-2.0 ppm, or 0.20-1.5 ppm, or 0.20-1.0 ppm, or 0.20-0.75 ppm, or 0.35-2.0 ppm, or 0.35-1.5 ppm, or 0.35-1.0 ppm, or 0.35-0.75 ppm.
[0227] In some embodiments, the polyethylene composition has 0.0015-2.4 ppm of hafnium.
[0228] In some embodiments, the polyethylene composition contains long-chain branching characterized by the long-chain branching factor (LCBF) disclosed herein. In embodiments of this disclosure, the upper limit of the LCBF of the polyethylene composition is 0.0400 (dimensionless).
[0229] In some embodiments, the LCBF of the polyethylene composition is at most 0.0375, or at most 0.0370, or at most 0.0350, or at most 0.0330, or at most 0.0300, or at most 0.0270, or at most 0.0250. In some embodiments, the LCBF of the polyethylene composition is less than 0.0400, or less than 0.0370, or less than 0.0350, or less than 0.0330, or less than 0.0300, or less than 0.0270, or less than 0.0250.
[0230] In some embodiments, the LCBF of the polyethylene composition is at least 0.0010, or at least 0.0030, or at least 0.0050, or at least 0.0060, or at least 0.0070, or at least 0.0080. In some embodiments, the LCBF of the polyethylene composition is greater than 0.0010, or greater than 0.0030, or greater than 0.0050, or greater than 0.0060, or greater than 0.0070, or greater than 0.0080.
[0231] In some embodiments, the LCBF of the polyethylene composition is 0.0010-0.0400, or 0.0030-0.0400, or 0.0050-0.0400, or 0.0050-0.0375, or 0.0060-0.0400, or 0.0070-0.0400, or 0.0010-0.0370, or 0.0030-0.0370. Or 0.0050-0.0370, or 0.0060-0.0370, or 0.0070-0.0370, or 0.0010-0.0350, or 0.0030-0.0350, or 0.0050-0.0350, or 0.0060-0.0350, or 0.0070-0.0350, or 0.0010-0.0330, or 0.00 30-0.0330, or 0.0050-0.0330, or 0.0060-0.0330, or 0.0070-0.0330, or 0.0010-0.0300, or 0.0030-0.0300, or 0.0050-0.0300, or 0.0060-0.0300, or 0.0070-0.0300, or 0.0010-0. 0270, or 0.0030-0.0270, or 0.0050-0.0270, or 0.0060-0.0270, or 0.0070-0.0270, or 0.0010-0.0250, or 0.0030-0.0250, or 0.0050-0.0250, or 0.0060-0.0250, or 0.0070-0.0250.
[0232] In some embodiments, the LCBF of the polyethylene composition is 0.0050-0.0375.
[0233] In some embodiments, the LCBF of the polyethylene composition is 0.0050-0.0350.
[0234] In some embodiments, the LCBF of the polyethylene composition is 0.0080-0.0350.
[0235] In some embodiments, the polyethylene composition has fractions that are eluted at temperatures above 95°C in CTREF analysis.
[0236] In some embodiments, the polyethylene composition has fractions that are eluted at temperatures below 90°C in CTREF analysis.
[0237] In some embodiments, the polyethylene composition has fractions eluted at about 95°C and fractions eluted at below 90°C in CTREF analysis.
[0238] In some embodiments, such as those measured by the Carreau-Yasuda model, the rheological width parameter (a) of the polyethylene composition is less than 0.450, or at most 0.450, or less than 0.425, or at most 0.425, or less than 0.400, or at most 0.400, or less than 0.375, or at most 0.375.
[0239] In some embodiments, such as those measured by the Carlo-Yasuda model, the rheological width parameter (a) of the polyethylene composition is at least 0.200, or greater than 0.200, or at least 0.225, or greater than 0.225, or at least 0.250, or greater than 0.250.
[0240] In some embodiments, such as those measured by the Carlo-Yasuda model, the rheological width parameter (a) of the polyethylene composition is 0.200-0.450, or 0.200-0.425, or 0.200-0.400, or 0.200-0.375, or 0.225-0.450, or 0.225-0.425, or 0.225-0.400, or 0.225-0.375, or 0.250-0.450, or 0.250-0.425, or 0.250-0.400, or 0.250-0.375.
[0241] In some embodiments, such as those measured by the Carlo-Yasuda model, the rheological width parameter (a) of the polyethylene composition is less than 0.450. In some embodiments, such as those measured by the Carlo-Yasuda model, the rheological width parameter (a) of the polyethylene composition is less than 0.400. In some embodiments, such as those measured by the Carlo-Yasuda model, the rheological width parameter (a) of the polyethylene composition is 0.200-0.400.
[0242] In some implementations, such as those using ASTM D1693 in 100% IGEPAL ® The environmental stress cracking resistance (ESCR) of the polyethylene composition or the sheet made from the polyethylene composition, as determined under condition A in CO-630, is greater than 500 hours, or greater than 600 hours, or greater than 700 hours, or greater than 800 hours, or greater than 900 hours, or greater than 1000 hours, or greater than 1100 hours, or greater than 1200 hours.
[0243] In some embodiments, such as those measured by ASTM D1693 in 100% IGEPAL CO-630 under condition A, the environmental stress cracking resistance (ESCR) of the polyethylene composition or the sheet made from the polyethylene composition is greater than 500 hours. In some embodiments, such as those measured by ASTM D1693 in 100% IGEPAL CO-630 under condition A, the environmental stress cracking resistance (ESCR) of the polyethylene composition or the sheet made from the polyethylene composition is greater than 1000 hours.
[0244] In some implementations, such as those determined by ASTM D1693 in 100% IGEPAL CO-630 under condition B, the environmental stress cracking resistance (ESCR) of the polyethylene composition or the sheet made from the polyethylene composition is greater than 500 hours, or greater than 600 hours, or greater than 700 hours, or greater than 800 hours, or greater than 900 hours, or greater than 1000 hours, or greater than 1100 hours, or greater than 1200 hours.
[0245] In some implementations, such as those determined by ASTM D1693 in 100% IGEPAL CO-630 under both Condition A and Condition B, the environmental stress cracking resistance (ESCR) of the polyethylene composition or the sheet made from the polyethylene composition is greater than 500 hours, or greater than 600 hours, or greater than 700 hours, or greater than 800 hours, or greater than 900 hours, or greater than 1000 hours, or greater than 1100 hours, or greater than 1200 hours.
[0246] In some implementations, such as those determined by ASTM D1693 in 100% IGEPAL CO-630 under Condition A or Condition B, the environmental stress cracking resistance (ESCR) of the polyethylene composition or the sheet made from the polyethylene composition is greater than 500 hours, or greater than 600 hours, or greater than 700 hours, or greater than 800 hours, or greater than 900 hours, or greater than 1000 hours, or greater than 1100 hours, or greater than 1200 hours.
[0247] In some implementations, such as those determined by ASTM D1693 in 10% IGEPAL CO-630 under condition A, the environmental stress cracking resistance (ESCR) of the polyethylene composition or the sheet made from the polyethylene composition is greater than 50 hours, or greater than 60 hours, or greater than 100 hours, or greater than 150 hours, or greater than 200 hours, or greater than 400 hours, or greater than 600 hours, or greater than 700 hours, or greater than 800 hours, or greater than 900 hours.
[0248] In some embodiments, such as those measured by ASTM D1693 in 10% IGEPAL CO-630 under condition A, the environmental stress cracking resistance (ESCR) of the polyethylene composition or the sheet made from the polyethylene composition is greater than 50 hours. In some embodiments, such as those measured by ASTM D1693 in 10% IGEPAL CO-630 under condition A, the environmental stress cracking resistance (ESCR) of the polyethylene composition or the sheet made from the polyethylene composition is greater than 100 hours.
[0249] In some implementations, such as those determined by ASTM D1693 in 10% IGEPAL CO-630 under condition B, the environmental stress cracking resistance (ESCR) of the polyethylene composition or the sheet made from the polyethylene composition is greater than 30 hours, or greater than 40 hours, or greater than 50 hours, or greater than 60 hours, or greater than 100 hours, or greater than 150 hours, or greater than 200 hours, or greater than 400 hours.
[0250] In some implementations, such as those determined by ASTM D1693 in 10% IGEPAL CO-630 under both Condition A and Condition B, the environmental stress cracking resistance (ESCR) of the polyethylene composition or the sheet made from the polyethylene composition is greater than 50 hours, or greater than 60 hours, or greater than 100 hours, or greater than 150 hours, or greater than 200 hours, or greater than 400 hours.
[0251] In some implementations, such as those determined by ASTM D1693 in 10% IGEPAL CO-630 under Condition A or Condition B, the environmental stress cracking resistance (ESCR) of the polyethylene composition or the sheet made from the polyethylene composition is greater than 50 hours, or greater than 60 hours, or greater than 100 hours, or greater than 150 hours, or greater than 200 hours, or greater than 400 hours.
[0252] In some embodiments, the polyethylene composition has a zero-shear viscosity (η0) of about 4,000 Pa·s to about 20,000 Pa·s at 190°C (inclusive of any narrower range within this range and any value covered by these ranges). For example, in some embodiments, the zero-shear viscosity (η0) of the polyethylene composition at 190°C is about 4,000 Pa·s to about 16,000 Pa·s, or about 4,000 Pa·s to about 14,000 Pa·s, or about 4,000 Pa·s to about 13,000 Pa·s, or about 6,000 Pa·s to about 20,000 Pa·s, or about 6,000 Pa·s to about 16,000 Pa·s, or about 6,000 Pa·s to about 14,000 Pa·s, or about 6,000 Pa·s to about 13,000 Pa·s, or about 7,000 Pa·s to about 20,000 Pa·s, or about 7,000 Pa·s to about 16,000 Pa·s, or about 7,000 Pa·s to about 14,000 Pa·s. Pa.s, or about 7,000 Pa.s to about 13,000 Pa.s, or about 8,000 Pa.s to about 20,000 Pa.s, or about 8,000 Pa.s to about 16,000 Pa.s, or about 8,000 Pa.s to about 14,000 Pa.s, or about 8,000 Pa.s to about 13,000 Pa.s, or about 10,000 Pa.s to about 20,000 Pa.s, or about 10,000 Pa.s to about 16,000 Pa.s, or about 10,000 Pa.s to about 14,000 Pa.s, or about 10,000 Pa.s to about 13,000 Pa.s.
[0253] In some embodiments, the relative elasticity (elasticity ratio G' / G”) of the polyethylene composition at 0.05 rad / s is at most 0.30, or at most 0.27, or at most 0.25, or at most 0.22, or at most 0.20. In some embodiments, the relative elasticity (elasticity ratio G' / G”) of the polyethylene composition at 0.05 rad / s is at most 0.25.
[0254] In some embodiments, the melt strength of the polyethylene composition is at least 0.75 cN, or at least 1.00 cN, or at least 1.25 cN, or at least 1.50 cN, or at least 1.75 cN, or at least 2.00 cN, or at least 2.25 cN, or at least 2.50 cN, or at least 2.75 cN.
[0255] In some embodiments, the melt strength of the polyethylene composition is 2.0-5.0 cN, or 2.0-4.0 cN, or 2.5-4.0 cN.
[0256] In some embodiments, the flexural secant modulus of the polyethylene composition or the sheet made from the polyethylene composition is at least 900 MPa, or greater than 900 MPa, or at least 950 MPa, or greater than 950 MPa, or at least 1000 MPa, or greater than 1000 MPa, or at least 1050 MPa, or greater than 1050 MPa, or at least 1100 MPa, or greater than 1100 MPa.
[0257] In some embodiments, the flexural secant modulus of the polyethylene composition or the sheet made from the polyethylene composition is 900-1400 MPa at 1% (inclusive of any narrower range within this range and any value covered by these ranges). For example, in some embodiments, the flexural secant modulus of the polyethylene composition or the sheet prepared from the polyethylene composition is 900-1300 MPa, or 900-1200 MPa, or 900-1150 MPa, or 950-1400 MPa, or 950-1300 MPa, or 950-1200 MPa, or 950-1150 MPa, or 1000-1400 MPa, or 1000-1300 MPa, or 1000-1200 MPa, or 1000-1150 MPa, or 1050-1400 MPa, or 1050-1300 MPa, or 1050-1200 MPa, or 1050-1150 MPa, or 1100-1400 MPa, or 1100-1300 MPa. MPa, or 1100-1200 MPa, or 1100-1150 MPa.
[0258] In some embodiments, the flexural secant modulus of the polyethylene composition or the sheet made from the polyethylene composition is at least 1000 MPa at 1%. In some embodiments, the flexural secant modulus of the polyethylene composition or the sheet made from the polyethylene composition is 1000-1300 MPa at 1%.
[0259] In some embodiments, the tensile secant modulus of the polyethylene composition or the sheet made from the polyethylene composition at 1% is at least 900 MPa, or greater than 900 MPa, or at least 950 MPa, or greater than 950 MPa, or at least 1000 MPa, or greater than 1000 MPa, or at least 1050 MPa, or greater than 1050 MPa, or at least 1100 MPa, or greater than 1100 MPa.
[0260] In some embodiments, the tensile secant modulus of the polyethylene composition or the sheet made from the polyethylene composition is 900-1500 MPa at 1% (inclusive of any narrower range within this range and any value covered by these ranges). For example, in some embodiments, the tensile secant modulus of the polyethylene composition or the sheet prepared from the polyethylene composition is 900-1400 MPa, or 900-1300 MPa, or 900-1250 MPa, or 950-1500 MPa, or 950-1400 MPa, or 950-1300 MPa, or 950-1250 MPa, or 1000-1500 MPa, or 1000-1400 MPa, or 1000-1300 MPa, or 1000-1250 MPa, or 1050-1500 MPa, or 1050-1400 MPa, or 1050-1300 MPa, or 1050-1250 MPa, or 1100-1500 MPa, or 1100-1400 MPa. MPa, or 1100-1300 MPa, or 1100-1250 MPa.
[0261] In some embodiments, the cantilever beam impact strength value (also referred to as cantilever beam impact value or cantilever beam impact strength) of the polyethylene composition or the sheet made from the polyethylene composition is ≥ 4.0 ft·lb / in, or > 4.0 ft·lb / in, or ≥ 5.0 ft·lb / in, or > 5.0 ft·lb / in, or ≥ 6.0 ft·lb / in, or > 6.0 ft·lb / in, or ≥ 6.5 ft·lb / in, or > 6.5 ft·lb / in.
[0262] In some embodiments, the cantilever beam impact strength of the polyethylene composition or the sheet made from the polyethylene composition is at least 4.0 ft·lb / in. In some embodiments, the cantilever beam impact strength of the polyethylene composition or the sheet made from the polyethylene composition is at least 6.0 ft·lb / in.
[0263] In some embodiments, the cantilever beam impact strength of the polyethylene composition or the sheet made from the polyethylene composition is 4.0-20.0 ft·lb / in (inclusive of any narrower range within this range and any value encompassed by these ranges). For example, in some embodiments, the cantilever beam impact strength of the polyethylene composition or the sheet made from the polyethylene composition is 4.0-18.0 ft·lb / in, or 4.0-16.0 ft·lb / in, or 4.0-14.0 ft·lb / in, or 4.0-13.0 ft·lb / in, or 5.0-20.0 ft·lb / in, or 5.0-18.0 ft·lb / in, or 5.0-16.0 ft·lb / in, or 5.0-14.0 ft·lb / in, or 5.0-1 3.0 ft·lb / inch, or 6.0–20.0 ft·lb / inch, or 6.0–18.0 ft·lb / inch, or 6.0–16.0 ft·lb / inch, or 6.0–14.0 ft·lb / inch, or 6.0–13.5 ft·lb / inch, or 6.5–20.0 ft·lb / inch, or 6.5–18.0 ft·lb / inch, or 6.5–16.0 ft·lb / inch, or 6.5–14.0 ft·lb / inch, or 6.5–13.0 ft·lb / inch.
[0264] In some embodiments, the cantilever beam impact strength of the polyethylene composition or the sheet made from the polyethylene composition is 4.0-13.0 ft·lb / in.
[0265] In some embodiments, the tensile impact strength (also referred to as tensile impact value or tensile impact strength) of the polyethylene composition or the sheet made from the polyethylene composition is ≥ 150 ft·lb / in. 2 or ≥ 175 ft·lb / in 2 or ≥ 200 ft·lb / in 2 or ≥ 215 ft·lb / in 2 or ≥ 230 ft·lb / in 2 or ≥ 240 ft·lb / in 2 .
[0266] In some embodiments, the tensile impact strength of the polyethylene composition or the sheet made from the polyethylene composition is at least 230 ft·lb / in. 2 .
[0267] In some embodiments, the tensile impact strength of the polyethylene composition or the sheet made from the polyethylene composition is 150-500 ft·lb / in. 2 or 150-450 ft·lb / inch 2 or 150-400 ft·lb / inch 2or 150-375 ft·lbs / inch 2 or 175-500 ft·lb / in 2 or 175-450 ft·lb / inch 2 or 175-400 ft·lb / inch 2 or 175-375 ft·lb / inch 2 or 200-500 ft·lb / inch 2 or 200-450 ft·lb / inch 2 or 200-400 ft·lb / inch 2 or 200-375 ft·lb / inch 2 or 215-500 ft·lb / in 2 or 215-450 ft·lb / inch 2 or 215-400 ft·lb / in 2 or 215-375 ft·lb / inch 2 or 230-500 ft·lb / inch 2 or 230-450 ft·lb / inch 2 or 230-400 ft·lb / in 2 or 230-375 ft·lb / inch 2 or 240-500 ft·lb / in 2 or 240-450 ft·lb / inch 2 or 240-400 ft·lb / in 2 or 240-375 ft·lb / inch 2 .
[0268] Optionally, additives may be added to the polyethylene composition. Additives may be added to the polyethylene composition during the extrusion or compounding step, but other suitable known methods will be apparent to those skilled in the art. Additives may be added as is or as part of a separate polymer component (i.e., not the first or second ethylene polymer described above) added during the extrusion or compounding step. Suitable additives are known in the art and include, but are not limited to, antioxidants, phosphites and phosphonites, nitrones, acid stabilizers, UV light stabilizers, UV absorbers, metal passivators, dyes, fillers and reinforcing agents, nanoscale organic or inorganic materials, antistatic agents, lubricants (e.g., calcium stearate), slip additives (e.g., erucamide), and nucleating agents (including nucleating reagents, pigments, or any other chemicals that can provide nucleation for the polyethylene composition). The amount of additives that may be optionally added is typically up to 20% by weight (wt%).
[0269] One or more nucleating agents can be introduced into a polyethylene composition by kneading a polymer (usually in powder or pellet form) with a mixture of nucleating agents that can be used alone or in the form of a concentrate containing further additives (e.g., stabilizers, pigments, antistatic agents, UV stabilizers, and fillers). The nucleating agent should be a material that is wetted or absorbed by the polymer, insoluble in the polymer, and has a melting point higher than that of the polymer, and should be uniformly dispersed in the polymer melt in the finest possible form (1-10 µm). Compounds known to have nucleating ability for polyolefins include salts of aliphatic monocarboxylic acids or dicarboxylic acids, or salts of arylalkyl acids, such as sodium succinate or aluminum phenylacetate; and alkali metal salts or aluminum salts of aromatic or alicyclic carboxylic acids, such as sodium β-naphthoate. Another compound known to have nucleating ability is sodium benzoate. The effectiveness of nucleation can be monitored microscopically by observing the degree of size reduction of the spherulites formed by the aggregation of microcrystals.
[0270] Examples of commercially available nucleating agents that can be added to polyethylene compositions are dibenzyl sorbitol esters (e.g., produced by Millicken Chemical under the trademark MILLAD). ® 3988 sells products and is manufactured by Ciba Specialty Chemicals under the trademark IRGACLEAR. ®(Products sold). Further examples of nucleating agents that can be added to polyethylene compositions include cyclic organic structures (and their salts, such as disodium bicyclic [2.2.1]heptenediacarboxylate) disclosed in U.S. Patent No. 5,981,636; saturated forms of structures disclosed in U.S. Patent No. 5,981,636 (as disclosed in U.S. Patent No. 6,465,551; Zhao et al., granted to Milliken); salts of certain cyclic dicarboxylic acids having a hexahydrophthalic acid structure (or “HHPA” structure) as disclosed in U.S. Patent No. 6,599,971 (Dotson et al., granted to Milliken); and phosphate esters, such as those disclosed in U.S. Patent No. 5,342,868 and those sold by Asahi Denka Kogyo under the trade names NA-11 and NA-21; cyclic dicarboxylic acids and their salts, such as divalent metal salts or metalloid salts (especially calcium salts) having an HHPA structure disclosed in U.S. Patent No. 6,599,971. For clarity, the HHPA structure typically comprises a ring structure having six carbon atoms in the ring and two carboxylic acid groups as substituents on adjacent atoms of the ring structure. As disclosed in U.S. Patent No. 6,599,971, the other four carbon atoms in the ring may be substituted. One example is calcium 1,2-cyclohexanedicarboxylate (CAS Registry No. 491589-22-1). Further examples of nucleating agents that can be added to polyethylene compositions include those disclosed in WO 2015042561, WO 2015042563, WO 2015042562, and WO 2011050042.
[0271] Many of the nucleating agents described above may be difficult to mix with nucleating polyethylene compositions, and it is known to use dispersing aids such as zinc stearate to mitigate this problem.
[0272] In some embodiments, the nucleating agent is fully dispersed in the polyethylene composition.
[0273] In some embodiments, the amount of nucleating agent used is relatively small (5-3000 ppm by weight [based on the weight of the polyethylene composition]), and those skilled in the art will recognize that care must be taken to ensure adequate dispersion of the nucleating agent. In some embodiments, the nucleating agent is added to the polyethylene composition in a finely ground form (less than 50 micrometers, particularly less than 10 micrometers) to promote mixing. This type of “physical blend” (i.e., a mixture of the nucleating agent and resin in solid form) is generally preferred over a “masterbatch” using a nucleating agent (where the term “masterbatch” refers to the practice of first melt-mixing the additive [in this case, the nucleating agent] with a small amount of the polyethylene composition resin, and then melt-mixing the “masterbatch” with the remaining majority of the polyethylene composition resin).
[0274] In some implementations, additives such as nucleating agents can be added to the polyethylene composition as a “masterbatch”, wherein the term “masterbatch” refers to the practice of first melt-mixing the additive (e.g., nucleating agent) with a small amount of the polyethylene composition, and then melt-mixing the “masterbatch” with the remaining majority of the polyethylene composition.
[0275] In some embodiments, the polymer composition further comprises a nucleating agent or a mixture of nucleating agents.
[0276] In some embodiments, polyethylene compositions are used in the molding of molded articles. For example, articles are intended to be formed by rotational molding, continuous compression molding, and injection molding. Such articles include, for example, cans from rotational molding, and bottle caps, screw caps, and seals from compression molding or injection molding. However, those skilled in the art will readily recognize that the compositions described above can also be used in other applications, such as, but not limited to, film, injection blow molding, blow molding, and sheet extrusion applications.
[0277] In some embodiments, the polyethylene compositions disclosed herein can be converted into molded articles.
[0278] In some embodiments, the polyethylene compositions disclosed herein can be used to manufacture articles by rotational molding.
[0279] In some embodiments, the polyethylene compositions disclosed herein can be converted into rotationally molded articles.
[0280] In some embodiments, and as an alternative to rotational molding, the polyethylene compositions disclosed herein can be used to manufacture articles by extrusion, compression molding or injection molding.
[0281] In some embodiments, and as an alternative to rotational molding, the polyethylene compositions disclosed herein can be used to prepare articles by blown film method.
[0282] Rotational Molding Products Typically, polyethylene compositions are manufactured in powder or pellet form for use in rotational molding processes. The rotational molding process may additionally include process steps for manufacturing the polyethylene composition. For rotational molding, powder is preferred, and it may have a particle size of 35 μm or less. Cryogenic grinding may be performed if necessary. The polymer powder is then placed inside a hollow mold and heated within the mold as it rotates. The mold typically rotates biaxially, i.e., simultaneously about two vertical axes. The mold is typically heated externally (usually in a forced-air circulation oven). Generally, the rotational molding process steps include: tumbling, heating, and melting of the polymer powder, followed by coalescence, fusion, or sintering and cooling to remove the molded article.
[0283] In some embodiments of this disclosure, the polyethylene compositions of this disclosure can be processed in a commercial rotary molding machine. The time and temperature used will depend on factors including the thickness of the rotationally molded part, and suitable processing conditions can be readily determined by those skilled in the art. By way of providing some non-limiting examples, the oven temperature range during the heating step can be 400℉-800℉ (204℃-427℃), or about 500℉-about 700℉ (about 260℃-about 371℃), or about 575℉-about 650℉ (about 302℃-about 343℃).
[0284] After the heating step, the mold is cooled. The part must be cooled sufficiently to be easily removed from the mold and retain its shape. The mold can be removed from the oven while it is continuously rotating. First, cold air is blown onto the mold. The air can be at ambient temperature. After the controlled cooling period of the mold by the air, a water spray can be used. Water cools the mold more rapidly. The water used can be at a cold tap water temperature, for example, it can be about 4°C (40℉) to about 16°C (60℉). After the water cooling step, another air cooling step can be used. This can be a short step, during which the equipment dries as heat is carried away by the evaporation of water.
[0285] The heating and cooling cycle times will depend on the equipment used and the molded article. Specific factors include the thickness of the part in the mold material. By way of providing a non-limiting example, the conditions for a ⅛-inch thick part in a steel mold could be to heat the mold in an oven with air at about 316°C (600℉) for about 15 minutes; then the part could be cooled in forced air at ambient temperature for about 8 minutes, and then cooled by tap water spray at about 10°C (50℉) for about 5 minutes; optionally, the part could be cooled in forced air at ambient temperature for an additional 2 minutes.
[0286] During the heating and cooling steps, it is preferable to continuously rotate the mold containing the molded article. Typically, this is done along two vertical axes. The rotational rate of the mold about each axis is limited by the machine's capabilities and the shape of the molded article. Typical, non-limiting operating ranges available in this disclosure involve rotating the main shaft to the secondary shaft in a ratio of about 1:8 to 10:1 or about 1:2 to 8:1.
[0287] Non-limiting examples of articles that can be prepared using rotational molding include custom cans, water tanks, trolleys, transport boxes and containers, coolers, and sports and recreational equipment (e.g., boats, kayaks), toys, and playground equipment.
[0288] The desired physical properties of rotationally molded products depend on the application of interest. Non-limiting examples of desired properties include: flexural modulus (1% and 2% secant modulus), environmental stress cracking resistance (ESCR); Shore hardness, heat deflection temperature (HDT), VICAT softening point, cantilever beam impact strength, ARM impact resistance, and color (whiteness and / or yellowness index).
[0289] In some embodiments, a polyethylene composition with a melt index (I2) of 1.0-3.0 g / 10min or less than 3.0 g / 10min is used to prepare rotationally molded articles having internal volumes of at least about 2,500 liters, or at least about 5,000 liters, or at least about 10,000 liters, or at least about 20,000 liters, or at least about 50,000 liters, or at least about 100,000 liters.
[0290] In some implementations, the rotationally molded product is a can. In some implementations, the rotationally molded product is a large can.
[0291] In some embodiments, polyethylene compositions with a melt index (I2) of 1.0-3.0 g / 10min or less than 3.0 g / 10min are used to prepare rotationally molded articles with an internal volume of less than about 1,000,000 liters or less than about 500,000 liters.
[0292] In some embodiments, the method for preparing a rotationally molded article includes the following steps: (i) loading a polyethylene composition into a mold; (ii) heating the mold in an oven to a temperature exceeding 280°C; (iii) rotating the mold about at least two axes; (iv) cooling the mold while it is rotating; and (v) opening the mold to demold the rotationally molded article.
[0293] Additives and auxiliaries – rotational molding products Depending on the intended use, the described polyethylene compositions and the resulting rotationally molded articles may optionally contain additives and auxiliaries. Additives may be added to the polyethylene composition during the extrusion or compounding step, but other suitable known methods will be apparent to those skilled in the art. Additives may be added as is or as part of a separate polymer component added during the extrusion or compounding step. Non-limiting examples of additives and auxiliaries include antiblocking agents, antioxidants, heat stabilizers, slip agents, processing aids, antistatic additives, colorants, dyes, filler materials, light stabilizers, heat stabilizers, light absorbers, lubricants, pigments, plasticizers, nucleating agents, and combinations thereof. Non-limiting examples of suitable primary antioxidants include IRGANOX. ®1010 [CAS Registry No. 6683-19-8] and IRGANOX 1076 [CAS Registry No. 2082-79-3]; both are available from BASF Corporation, Florham Park, NJ, USA. Non-limiting examples of suitable co-antioxidants include IRGANOX. ® 168 [CAS Registry No. 31570-04-4], available from BASF Corporation, Florham Park, NJ, USA; Weston 705 [CAS Registry No. 939402-02-5], available from SI Group, The Woodlands, TX, USA; and DOVERPHOS ® LGP-11 [CAS Registry No. 1227937-46-3] is available from Dover Chemical Corporation, Dover OH, USA. Optional additives are typically added in amounts up to 20% by weight (wt%).
[0294] One or more nucleating agents can be introduced into a polyethylene composition by kneading a polymer (usually in powder or pellet form) with a mixture of nucleating agents that can be used alone or in the form of a concentrate containing further additives (e.g., stabilizers, pigments, antistatic agents, UV stabilizers, and fillers). The nucleating agent should be a material that is wetted or absorbed by the polymer, insoluble in the polymer, and has a melting point higher than that of the polymer, and should be uniformly dispersed in the polymer melt in the finest possible form (1-10 µm). Compounds known to have nucleating ability for polyolefins include salts of aliphatic monocarboxylic acids or dicarboxylic acids, or salts of arylalkyl acids, such as sodium succinate or aluminum phenylacetate; and alkali metal salts or aluminum salts of aromatic or alicyclic carboxylic acids, such as sodium β-naphthoate. Another compound known to have nucleating ability is sodium benzoate. The effectiveness of nucleation can be monitored microscopically by observing the degree of size reduction of the spherulites formed by the aggregation of microcrystals.
[0295] In some embodiments, the described polyethylene compositions and the resulting rotationally molded articles may contain additives selected from the following: antioxidants, phosphites and phosphonites, nitrone, acid stabilizers, UV light stabilizers, UV absorbers, metal passivators, dyes, fillers and reinforcing agents, nanoscale organic or inorganic materials, antistatic agents, release agents (e.g., zinc stearate), and nucleating agents (including nucleating reagents, pigments, or any other chemicals that can provide nucleation for the polyethylene composition).
[0296] In some implementations, the amount of additive that can be added is up to 20% by weight (wt%).
[0297] Additives can be added to the polyethylene composition during the extrusion or compounding step, but other suitable known methods will be apparent to those skilled in the art. Additives can be added as is or as part of a separate polymer component added during the extrusion or compounding step.
[0298] A more detailed list of additives that can be added to the polyethylene compositions disclosed herein and used in rotationally molded articles is as follows: Phosphites (e.g., aryl monophosphites) As used herein, the term monophosphite aryl ester refers to a phosphite stabilizer containing: (1) only one phosphorus atom per molecule; and (2) at least one aryloxy group (which may also be referred to as phenoxy group) bonded to phosphorus.
[0299] In some embodiments, the monoaryl phosphite contains three aryl groups – for example, triphenyl phosphite is the simplest member of this preferred group of monoaryl phosphite esters.
[0300] In some embodiments, the monophosphite aryl ester contains C1-C on at least one aryl group. 10 Alkyl substituents. These substituents can be straight-chain (as in the case of nonyl substituents) or branched (e.g., isopropyl or tert-butyl substituents).
[0301] Non-limiting examples of monoaryl phosphites that may be used in embodiments of this disclosure include those selected from: triphenyl phosphite; diphenylalkyl phosphite; phenyl dialkyl phosphite; tri(nonylphenyl) phosphite [WESTON 399, available from SI Group]; tris(2,4-di-tert-butylphenyl) phosphite [IRGAFOS 168, available from Ciba Specialty Chemicals Corp.]; and bis(2,4-di-tert-butyl-6-methylphenyl) phosphite [IRGAFOS 38, available from BASF Corp.]; and 2,2',2"-hypo-nitro[triethyltri(3,3',5,5'-tetra-tert-butyl-1,1'-biphenyl-2,2'-diyl) phosphite [IRGAFOS 12, available from BASF Corp.].
[0302] In some embodiments, the amount of aryl monophosphite added to the polyethylene composition is 200-2,000 ppm (based on the weight of the polymer), or 300-1,500 ppm, or 400-1,000 ppm.
[0303] Phosphites, phosphonites (e.g., diphosphites, diphosphonites) As used herein, the term diphosphite refers to a phosphite stabilizer containing at least two phosphorus atoms per phosphite molecule (and similarly, the term diphosphonite refers to a phosphonite stabilizer containing at least two phosphorus atoms per phosphonite molecule).
[0304] Non-limiting examples of diphosphites and diphosphonates that may be used in embodiments of this disclosure include those selected from: distearate pentaerythritol diphosphite, diisodecyl pentaerythritol diphosphite, bis(2,4-di-tert-butylphenyl) pentaerythritol diphosphite [ULTRANOX] ® 626, available from SI Group]; bis(2,6-di-tert-butyl-4-methylphenyl) pentaerythritol diphosphite; bis(isodecoxy) pentaerythritol diphosphite, bis(2,4-di-tert-butyl-6-methylphenyl) pentaerythritol diphosphite, bis(2,4,6-tri-tert-butylphenyl) pentaerythritol diphosphite, tetrakis(2,4-di-tert-butylphenyl)4,4'-biphenyl-diphosphite [HOSTANOX P-EPQ] ® It is available from Clariant and pentaerythritol diphosphite bis(2,4-dicumylphenyl) diphosphite [DOVERPHOS S9228-T or DOVERPHOS S9228-CT] and P-EPQ (CAS No 119345-01-06) (which is an example of a commercially available diphosphite).
[0305] In some embodiments, the amount of diphosphite and / or diphosphonate added to the polyethylene composition is 200 ppm to 2,000 ppm (based on the weight of the polymer), or 300 to 1,500 ppm, or 400 to 1,000 ppm.
[0306] In some implementations, the use of diphosphites is preferred over the use of diphosphonates.
[0307] In some implementations, the most preferred diphosphites are those available under the trademarks DOVERPHOS S9228-CT and ULTRANOX 626.
[0308] Hindered phenolic antioxidants Hindered phenolic antioxidants can be any molecule commonly used as a primary antioxidant for stabilizing polyolefins. Suitable examples include 2,6-di-tert-butyl-4-methylphenol, 2-tert-butyl-4,6-dimethylphenol, 2,6-di-tert-butyl-4-ethylphenol, 2,6-di-tert-butyl-4-n-butylphenol, 2,6-di-tert-butyl-4-isobutylphenol, 2,6-dicyclopentyl-4-methylphenol, 2-(1-methylcyclohexyl)-4,6-dimethylphenol, 2,6-di(octadecyl)-4-methylphenol, 2,4,6-tricyclohexylphenol, and 2,6-di-tert-butyl-4-methoxymethylphenol.
[0309] Two (non-limiting) examples of suitable hindered phenolic antioxidants that can be used in embodiments of this disclosure are marketed by BASF Corporation under the trademarks IRGANOX 1010 (CAS Registry No. 6683-19-8) and IRGANOX 1076 (CAS Registry No. 2082-79-3).
[0310] In some embodiments, the amount of hindered phenolic antioxidant added to the polyethylene composition is 100-2000 ppm or 400-1000 ppm (based on the weight of the polymer).
[0311] Long-term stabilizers In some embodiments of this disclosure, plastic components intended for long-term use may contain at least one hindered amine light stabilizer (HALS). HALS are well known to those skilled in the art.
[0312] When adopted, in some implementations, HALS can be commercially available materials and can be used in a conventional manner and in conventional quantities.
[0313] Commercially available HALS that may be used in embodiments of this disclosure include those produced by BASF Corporation under the trademark CHIMASSORB ® 119; CHIMASSORB 944; CHIMASSORB 2020; TINUVIN ® Those sold under the 622 and TINUVIN 770 brands; and those sold by Solvay under the trademark CYASORB ® Those marketed as UV 3346, CYASORB UV 3529, CYASORB UV 4801, and CYASORBUV 4802. In some embodiments of this disclosure, TINUVIN 622 is preferred. In other embodiments of this disclosure, mixtures of more than one HALS are also contemplated.
[0314] In some embodiments, suitable HALS include those selected from: bis(2,2,6,6-tetramethylpiperidinyl) sebacate; bis-5(1,2,2,6,6-pentamethylpiperidinyl) sebacate; bis(1,2,2,6,6-pentamethylpiperidinyl) n-butyl-3,5-di-tert-butyl-4-hydroxybenzylmalonate; condensation product of 1-hydroxyethyl-2,2,6,6-tetramethyl-4-hydroxy-piperidine and succinic acid; N,N'-(2,2,6,6-tetramethylpiperidinyl) The condensation product of hexamethylenediamine and 4-tert-octylamino-2,6-dichloro-1,3,5-s-triazine; tris(2,2,6,6-tetramethylpiperidyl)-nitrotriacetate, tetrakis-(2,2,6,6-tetramethyl-4-piperidyl)-1,2,3,4-butane-tetra-arbonic acid; and 1,1'(1,2-ethylenediyl)-bis(3,3,5,5-tetramethylpiperidone).
[0315] hydroxylamine Hydroxylamine and its derivatives (including amine oxides) are known to be used as additives in polyethylene compositions for the preparation of rotomolded parts, as disclosed, for example, in embodiments of U.S. Patent No. 6,444,733 and this disclosure, and the hydroxylamine and its derivatives disclosed therein are also suitable for use.
[0316] In some embodiments, the useful hydroxylamine for inclusion in the polyethylene composition may be selected from N,N-dialkylhydroxylamine, a commercially available example of which is N,N-dialkylhydroxylamine sold by BASF as IRGASTAB FS 042, and which is reported to be prepared by the direct oxidation of N,N-di(hydrogenated) tallow amine.
[0317] Additive package In some embodiments, the polyethylene composition contains an additive package comprising: hindered monophosphite, diphosphite, hindered amine light stabilizer, and at least one additional additive selected from hindered phenols and hydroxylamine.
[0318] In some implementations, the additive package contains hydroxylamine.
[0319] In some implementations, the hydroxylamine is N,N-dialkylhydroxylamine.
[0320] In some implementations, hydroxylamine is IRGASTAB FS 042 (BASF).
[0321] In some embodiments, the concentration of hydroxylamine, by weight, is at least about 400 ppm, or at least about 500 ppm, or at least about 600 ppm, or at least about 700 ppm, or at least about 750 ppm, or at least about 800 ppm.
[0322] In some implementations, the concentration of hydroxylamine is at least about 750 ppm by weight.
[0323] In some embodiments, the concentration of hydroxylamine, by weight, is about 400 ppm, or about 500 ppm, or about 600 ppm, or about 700 ppm, or about 750 ppm, or about 800 ppm.
[0324] In embodiments of this disclosure, the amount of hydroxylamine added to the polyethylene composition is 100-2,000 ppm, or 400-1,000 ppm, or 600-1,000 ppm, or 700-1,000 ppm, or 800-1,000 ppm by weight.
[0325] Features disclosed in the foregoing description or the following claims or drawings, expressed in their specific form, or expressed with respect to the means for implementing the disclosed functions or the methods or processes for obtaining the disclosed results, may, where appropriate, be used alone or in any combination of such features to implement the invention in its various forms.
[0326] While the invention has been described in conjunction with the exemplary embodiments described above, many equivalent modifications and variations will be apparent to those skilled in the art upon presentation of this disclosure. Therefore, the exemplary embodiments of the invention set forth above are to be considered illustrative rather than restrictive. Various changes may be made to the described embodiments without departing from the spirit and scope of the invention.
[0327] To avoid any doubt, any theoretical explanations provided herein are offered for the purpose of improving the reader's understanding. The inventors do not wish to be bound by any of these theoretical explanations.
[0328] Any section headings used in this document are for organizational purposes only and should not be construed as limiting the subject matter described.
[0329] Throughout this specification (including the following claims), unless the context otherwise requires, the words “comprise” and “include”, as well as variations such as “comprises” and “comprising”, shall be understood to imply inclusion of the stated whole element or step, or a group of whole elements or steps, but not to exclude any other whole element or step, or a group of whole elements or steps.
[0330] It is important to note that, unless the context clearly indicates otherwise, the singular forms “a” and “the” as used in the specification and appended claims include plural references. A range herein may be expressed as from “about” one particular value and / or to “about” another particular value. When such a range is expressed, another embodiment includes from one particular value and / or to another particular value. Similarly, when a value is expressed as an approximation using the antecedent “about,” it will be understood that the particular value forms another embodiment. The term “about” in relation to numerical values is optional and indicates, for example, + / −10%.
[0331] Further non-limiting details of this disclosure are provided in the following embodiments. The embodiments are presented for the purpose of illustrating selected embodiments of this disclosure; it should be understood that the presented embodiments do not limit the presented claims.
[0332] Example General test program Prior to testing, each polymer specimen was conditioned at 23±2°C and 50±10% relative humidity for at least 24 hours, and subsequently tested at 23±2°C and 50±10% relative humidity. In this document, the term "ASTM condition" refers to a laboratory maintained at 23±2°C and 50±10% relative humidity; and the specimens to be tested were conditioned in this laboratory for at least 24 hours prior to testing. ASTM refers to the American Society for Testing and Materials.
[0333] density The density of the polyethylene composition was determined using ASTM D792-13 (November 1, 2013).
[0334] Melt index Melt index of polyethylene compositions was determined using ASTM D1238 (August 1, 2013). Melt indices I2, I6, and I7 were measured at 190°C using weights of 2.16 kg, 6.48 kg, 10 kg, and 21.6 kg, respectively. 10 and I 21 In this document, the term "stress index" or its acronym "S.Ex." is defined by the following relationship: S.Ex. = log (I6 / I2) / log(6480 / 2160), where I6 and I2 are the melt flow rates measured at 190°C using loads of 6.48 kg and 2.16 kg, respectively. In this disclosure, the melt index may be expressed in units of g / 10 min, g / 10 min, dg / min, or dg / min (these units are equivalent).
[0335] Gel permeation chromatography (GPC) The molecular weight M of the polyethylene composition was determined using ASTM D6474-12 (December 15, 2012). n M w and M z and polydispersity (M w / M n Polymer sample solutions (1–2 mg / mL) were prepared by heating the polymer in 1,2,4-trichlorobenzene (TCB) and rotating it on a wheel in an oven at 150 °C for 4 hours. The antioxidant 2,6-di-tert-butyl-4-methylphenol (BHT) was added to the mixture to stabilize the polymer and prevent oxidative degradation. The BHT concentration was 250 ppm. TCB was used as the mobile phase at a flow rate of 1.0 mL / min, and differential refractive index (DRI) (detector) was used as the concentration detector on four SHODEX detectors. ® The sample solutions were analyzed by chromatography at 140 °C using a PL 220 high-temperature chromatography system with columns (HT803, HT804, HT805, and HT806). BHT was added to the mobile phase at a concentration of 250 ppm to protect the GPC columns from oxidative degradation. The sample injection volume was 200 µL. Chromatography was performed using CIRRUS. ® GPC software processes raw GPC data. GPC columns are calibrated using narrow-distribution polystyrene standards. The polystyrene molecular weight is converted to polyethylene molecular weight using the Mark-Hovink equation, as described in ASTM D6474-12 (December 15, 2012).
[0336] Triple Detection Size Exclusion Chromatography (3D-SEC) Polyethylene composition sample (polymer) solutions (1-3 mg / mL) were prepared by heating the polymer in 1,2,4-trichlorobenzene (TCB) and rotating it on a turntable in an oven at 150 °C for 4 hours. An antioxidant (2,6-di-tert-butyl-4-methylphenol (BHT)) was added to the mixture to stabilize the polymer and prevent oxidative degradation. The BHT concentration was 250 ppm. The sample solutions were chromatographically analyzed at 140 °C using a PL 220 high-temperature chromatography system equipped with a differential refractive index (DRI) detector, dual-angle light scattering detectors (15° and 90°), and a differential viscometer. The SEC columns used were four SHODEX columns (HT803, HT804, HT805, and HT806) or four PL Mixed ALS or BLS columns. TCB was used as the mobile phase at a flow rate of 1.0 mL / min, and BHT at a concentration of 250 ppm was added to the mobile phase to protect the SEC column from oxidative degradation. The sample injection volume was 200 µL. Raw SEC data were processed using CIRRUS GPC software to produce absolute molar mass and intrinsic viscosity [η]. The term "absolute" molar mass is used to distinguish the absolute molar mass determined by 3D-SEC from the molar mass determined by conventional SEC. The viscosity-average molar mass (Mi) determined by 3D-SEC was used in the calculations. v To determine the long-chain branching factor (LCBF).
[0337] GPC-FTIR A polyethylene composition (polymer) solution (2–4 mg / mL) was prepared by heating the polymer in 1,2,4-trichlorobenzene (TCB) and rotating it on a turntable in an oven at 150 °C for 4 hours. The antioxidant 2,6-di-tert-butyl-4-methylphenol (BHT) was added to the mixture to stabilize the polymer and prevent oxidative degradation. The BHT concentration was 250 ppm. The sample solution was chromatographically analyzed at 140 °C using TCB as the mobile phase at a flow rate of 1.0 mL / min on a Waters GPC 150C chromatograph equipped with four SHODEX columns (HT803, HT804, HT805, and HT806). The detection system consisted of a heated transfer line connected to the chromatographic apparatus and a heated FTIR flow cell. BHT at a concentration of 250 ppm was added to the mobile phase to protect the SEC column from oxidative degradation. The sample injection volume was 300 µL. The raw FTIR spectra were processed using OPUS FTIR software, and the polymer concentration and methyl content were calculated in real time using Chemometric software (PLS technique) associated with OPUS. The polymer concentration and methyl content were then acquired and baseline corrected using CIRRUS GPC software. The SEC column was calibrated using narrow-distribution polystyrene standards. The polystyrene molecular weight was converted to polyethylene molecular weight using the Mark-Hovink equation, as described in ASTM standard test method D6474. The comonomer content was calculated based on the polymer concentration and methyl content predicted using the PLS technique as described in Paul J. DesLauriers, Polymer 43, pp. 159-170 (2002) (incorporated herein by reference).
[0338] The GPC-FTIR method measures the total methyl content, which includes methyl groups located at the ends of major molecular chains, i.e., methyl terminal groups. Therefore, the original GPC-FTIR data must be corrected by subtracting the contribution from methyl terminal groups. For clarity, the original GPC-FTIR data overestimate the amount of short-chain branching (SCB), and this overestimation increases as the molecular weight (M) decreases. In this disclosure, 2-methyl correction is used to correct the original GPC-FTIR data. At a given molecular weight (M), the methyl terminal group (N) is calculated using the following equation. E The number of ) is N. E = 28000 / M, and N is subtracted from the original GPC-FTIR data. E (M-dependent) to generate SCB / 1000C (2-methyl corrected) GPC-FTIR data.
[0339] Unsaturated content The amount of unsaturated groups (i.e., double bonds) in polyethylene compositions was determined according to ASTM D3124-98 (Vinylene Unsaturation, March 2011) and ASTM D6248-98 (Vinyl and Trans Unsaturation, July 2012). Polymer samples were first subjected to carbon disulfide extraction to remove additives that might interfere with the analysis; (b) the samples (in pellet, film, or granule form) were pressed into plates with a uniform thickness (0.5 mm); and (c) the plates were analyzed by FTIR.
[0340] Comonomer content: Fourier transform infrared (FTIR) spectroscopy The amount of copolymer monomers in the polyethylene composition was determined by FTIR and reported as short-chain branching (SCB) content in units of CH3# / 1000C (number of methyl branches per 1000 carbon atoms). This test was performed according to ASTM D6645-01 (2001) using a compression-molded polymer sheet and a Thermo-Nicolet 750 Magna-IR spectrophotometer. The polymer sheet was prepared using a compression molding apparatus (Wabash-Genesis Series press) according to ASTM D4703-16 (April 2016).
[0341] Compositional Distribution Branching Index (CDBI) determined by CTREF The Compositional Distribution Branching Index (CDBI) of the disclosed examples and comparative examples was determined using a commercially available crystallization-TREF apparatus (“CTREF apparatus”) from Polymer Char (Valencia, Spain). The acronym “TREF” refers to Temperature Elution Fractionation. A sample of the polyethylene composition (80-100 mg) was placed in the reactor of the Polymer Char crystallization-TREF apparatus (containing 35 mL of 1,2,4-trichlorobenzene (TCB)), heated to 150°C, and maintained at that temperature for 2 hours to dissolve the sample. An aliquot of the TCB solution (1.5 mL) was then loaded into a Polymer Char TREF column filled with stainless steel beads, and the column was equilibrated at 110°C for 45 minutes. The polyethylene composition was then crystallized from the TCB solution in the column by slowly cooling the TREF column from 110°C to 30°C at a cooling rate of 0.09°C / min. The TREF column was then equilibrated at 30°C for 30 minutes. The crystallized polyethylene composition was then eluted from the TREF column as follows: the column temperature was slowly increased from 30°C to 120°C at a heating rate of 0.25°C / min while pure TCB solvent was passed through the column at a flow rate of 0.75 mL / min. TREF distribution curves were generated using PolymerChar software as the polyethylene composition eluted from the TREF column; that is, the TREF distribution curve is a graph showing the amount (or intensity) of the polymer material eluted from the column as a function of the TREF elution temperature. The CDBI was calculated from the TREF distribution curves for each analyzed polyethylene composition. 50 CDBI 50 "The percentage of the polymer whose composition is within 50% of the median comonomer composition (25% on each side of the median comonomer composition); it is calculated from the TREF composition profile and the normalized cumulative integral of the TREF composition profile. Those skilled in the art will understand that a calibration profile is needed to convert the TREF elution temperature into comonomer content, i.e., the amount of comonomer in the polyethylene composition fraction eluted at a specific temperature. The generation of such calibration profiles is described in the prior art (e.g., Wild, et al., J. Polym. Sci., Part B, Polym. Phys., Vol. 20(3), pp. 441-455).
[0342] Crystallization elution fractionation (CEF) Crystallization-elution fractionation (CEF), also referred to as TREF-CEF in this text, involves weighing a polymer sample (20–25 mg) into a vial and loading it onto the autosampler of a Polymer Char CEF device. The vial contains 6–7 mL of 1,2,4-trichlorobenzene (TCB) and is heated to the desired dissolution temperature (e.g., 160 °C) for 2 hours at a shaking rate of grade 3. The solution (0.5 mL) is then loaded into a CEF column (two CEF columns purchased from Polymer Char and installed in series). After equilibration at a given stable temperature (e.g., 115 °C) for 5 minutes, the polymer solution is allowed to crystallize as the temperature decreases from the stable temperature to 30 °C. After equilibration at 30 °C for 10 minutes, the crystallized sample is eluted with TCB as the temperature is increased from 30 °C to 110 °C. At the end of the run, the CEF column is cleaned for 5 minutes at 150 °C. Other CEF operating conditions were as follows: cooling rate 0.5 °C / min, flow rate during crystallization 0.02 mL / min, heating rate 1.0 °C / min, and flow rate during elution 2.0 mL / min. Data was processed using an Excel spreadsheet.
[0343] Hexane extractables Hexane extractables shall be determined in accordance with Code of Federal Registration 21 CFR §177.1520 Para (c) 3.1 and 3.2, wherein the amount of hexane extractables in the sample shall be determined by gravimetric analysis.
[0344] Neutron activation analysis (NAA) Neutron activation analysis (NAA) was used to determine catalyst residues in polyethylene compositions and was performed as follows: The polymer sample was placed in a radiation vial (composed of ultrapure polyethylene, 7 mL internal volume), and the sample weight was recorded. Using a pneumatic transfer system, the sample was placed inside a SLOWPOKE™ nuclear reactor (Atomic Energy of Canada Limited, Ottawa, Ontario, Canada) and irradiated with short-half-life elements (e.g., Ti, V, Al, Mg, and CI) for 30–600 seconds or with long-half-life elements (e.g., Zr, Hf, Cr, Fe, and Ni) for 3–5 hours. The average thermal neutron flux within the reactor was 5 × 10⁻⁶. 11 / cm 2 / s. After irradiation, the samples were removed from the reactor and aged to allow for radioactivity decay; short-half-life elements were aged for 300 seconds or long-half-life elements for several days. After aging, the gamma-ray spectra of the samples were recorded using a germanium semiconductor gamma-ray detector (Ortec model GEM55185, Advanced Measurement Technology Inc., Oak Ridge, Tenn., USA) and a multichannel analyzer (Ortec model DSPEC Pro). The amounts of each element in the samples were calculated from the gamma-ray spectra and recorded as parts per million relative to the total weight of the polymer sample. The NAA system was calibrated using Specpure standards (1000 ppm solutions of the desired element (greater than 99% pure)). 1 mL of the solution (element of interest) was pipetted onto 15 mm × 800 mm rectangular filter paper and air-dried. The filter paper was then placed in a 1.4 mL polyethylene irradiation vial and analyzed using the NAA system. The sensitivity of the NAA procedure (in counts / μg) was determined using the standards.
[0345] Dynamic Mechanical Analysis (DMA) Oscillatory shear measurements were performed at small strain amplitudes to obtain the linear viscoelastic function at 190 °C in a N2 atmosphere (strain amplitude of 10% and frequency range of 0.02–126 rad / s, 5 points per decibel). Frequency sweep experiments were conducted using a TA Instruments DHR3 stress-controlled rheometer with a cone geometry of 5° cone angle, 137 μm truncated section, and 25 mm diameter. In this experiment, sinusoidal strain waves were applied, and the stress response was analyzed according to the linear viscoelastic function. The zero-shear rate viscosity (η0) based on the DMA frequency sweep results was predicted using the Ellis model (see RB Bird et al., “Dynamics of Polymer Liquids. Vol. 1: Fluid Mechanics”, Wiley-Interscience Publications (1987), p. 228) or the Carlo-Yasuda model (see K. Yasuda (1979) doctoral dissertation, IT Cambridge). Dynamic rheological data were analyzed using rheometer software (i.e., Rheometrics RHIOS V4.4 or Orchestrator software) to determine the melt elastic modulus G' (G''=500) at a reference melt viscous modulus (G'') value of G''=500 Pa. If necessary, this value was obtained by interpolation between available data points using Rheometrics software. The term "storage modulus" G'(co), also known as "elastic modulus," is a function of the applied oscillation frequency co and is defined as the stress in phase with strain during sinusoidal deformation divided by the strain; while the term "viscous modulus" G''(ω), also known as "loss modulus," is also a function of the applied oscillation frequency ω and is defined as the stress 90 degrees out of phase with strain divided by the strain. These two moduli, along with other linear viscoelastic dynamic rheological parameters, are well known to those skilled in the art, for example, as discussed in Chapter 10 of G. Marin’s book, “Oscillatory Rheometry” (edited by AA Collyer and DW Clegg, Elsevier, 1988), on rheological measurements.
[0346] The shear thinning index SHI (1,100) The shear thinning index (SHI) is calculated as the ratio of the estimated complex viscosity at 1 kPa shear stress to the estimated complex viscosity at 100 kPa shear stress. (1,100) This provides information about the shear-thinning behavior of the polymer melt. High values indicate a strong dependence of viscosity on changes in deformation rate (shear or frequency).
[0347] The assessment of relative elasticity is based on measurements taken at low frequencies, which are most relevant to the conditions associated with powder sintering and densification in rotational molding. The relative elasticity assessment is based on the ratio of G' to G'' at frequencies of 0.05 rad / s (or 0.5 rad / s) from DMA frequency scan measurements taken at 190 °C. Data reported in the literature indicate that resin compositions with high relative elasticity tend to exhibit processing difficulties in terms of slow powder densification. Wang and Kontopoulou (2004) reported sufficient rotational molding properties for blends characterized as having a relative elasticity as high as 0.125. In this study, the effect of plasmon content on the rotational molding properties of polypropylene was investigated (WQ Wang and M. Kontopoulou (2004) Polymer Engineering and Science, Vol. 44, No. 9, pp. 1662-1669). Further analysis of the results published by Wang and Kontopoulou showed that compositions with higher plastite content exhibited increased relative elasticity (Gʹ / Gʺ>0.13) and correspondingly increased difficulty in achieving full densification during rotational molding evaluation.
[0348] In this disclosure, η0, as determined by DMA, is used to determine LCBF (long chain branching factor) (see U.S. Patent No. 10,442,921).
[0349] melt strength Melt strength was measured at 190°C using a Rosand RH-7 capillary rheometer (barrel diameter = 15 mm) with a flat die having a 2 mm diameter and an L / D ratio of 10:1. Pressure sensor: 10,000 psi (68.95 MPa). Piston speed: 5.33 mm / min. Traction angle: 52°. Traction increment speed: 50-80 m / min 2 or 65±15 m / min 2 The polymer melt is extruded through a capillary die at a constant rate, and then the polymer strand is pulled at an increasing traction speed until it breaks. The maximum steady-state value of the force in the plateau region of the force vs. time curve is defined as the melt strength of the polymer. The melt strength-to-stretch ratio is defined as the ratio of the velocity at the pulley to the velocity at the die exit.
[0350] Long-chain branching factor (LCBF) The LCBF (dimensionless) of the polyethylene composition was determined using the method described in U.S. Patent No. 10,442,921 (which is incorporated herein by reference).
[0351] As fully described in the paragraphs below, the calculation of the long-chain branching factor (“LCBF”) requires a polydispersity-corrected zero-shear viscosity (ZSV). c Intrinsic viscosity (IV) corrected for short-chain branching (“SCB”) and short-chain branching (“SCB”) c ).
[0352] As shown in equation Eq. (1), the zero-shear viscosity ZSV with dimensions of poise is... c Implement corrections: Eq. (1) Where η0 (zero shear viscosity (poise)) is measured by DMA as described above; Pd is the dimensionless polydispersity (MPa) measured using conventional GPC as described above. w / M n ); 1.8389 and 2.4110 are dimensionless constants.
[0353] As shown in equation Eq. (2), for the intrinsic viscosity IV in dL / g... c Implement corrections: Eq. (2) The intrinsic viscosity [η] (dL / g) was measured using the 3D-SEC method described above; the SCB was dimensionless (CH3# / 1000C) and determined using FTIR as described above; M v (Viscosity-average molar mass (g / mol)) was determined using 3D-SEC as described above; A is a dimensionless constant depending on the α-olefin in the ethylene / α-olefin copolymer sample, i.e., 2.1626, 1.9772, or 1.1398 for 1-octene, 1-hexene, and 1-butene α-olefins, respectively. In the case of ethylene homopolymers, no correction for the Mark-Hovink constant is required, i.e., SCB is 0.
[0354] "Linear" ethylene copolymers (or linear ethylene homopolymers) containing no LCB or containing undetectable levels of LCB fall on the reference line defined by Eq. (3): Eq. (3) The calculation of LCBF is based on the horizontal displacement (S) from the linear reference line as defined by the following equation. h ) and vertical displacement (S v ): Eq. (4) Eq. (5) In Eq. (4) and Eq. (5), ZSV is required. cand IV c The dimensions are poise and dL / g, respectively.
[0355] Horizontal displacement (S) h ) is at a constant intrinsic viscosity (IV) C ZSV c The displacement. If one removes the Log function, its physical meaning becomes clear: the two zero-shear viscosities (ZSV of the test sample) are... c Compared to having the same IV c ZSV of linear ethylene copolymers (or linear ethylene homopolymers) c The ratio of horizontal displacement (S). h () is dimensionless.
[0356] Vertical displacement (S) v At constant zero shear viscosity (ZSV) C IV c The displacement. If one removes the Log function, its physical meaning becomes clear: two intrinsic viscosities (with the same ZSV) are... c IV of linear ethylene copolymers (or linear ethylene homopolymers) c IV relative to the test sample c The ratio of vertical displacement (S) to vertical displacement (S). v () is dimensionless.
[0357] Defined by Eq. (6): Dimensionless Long Chain Branching Factor (LCBF) Eq. (6) In some embodiments of this disclosure, ethylene polymers (e.g., polyethylene compositions) having an LCB are characterized as having an LCBF ≥ 0.0010 (dimensionless); in contrast, ethylene polymers without an LCB (or with an undetectable LCB) are characterized as having an LCBF < 0.0010 (dimensionless).
[0358] Impact properties The impact properties of cantilever beams were determined according to ASTM D256. The cantilever beam impact specimens were notched to promote stress concentration points, inducing brittle fracture rather than ductile fracture.
[0359] Tensile impact properties were determined according to ASTM D1822.
[0360] Tensile properties The following tensile properties were determined using ASTM D638: yield elongation (%), yield strength (MPa), ultimate elongation (%), ultimate strength (MPa), and 1% and 2% secant modulus (MPa).
[0361] Bending properties The bending properties, i.e., 2% secant modulus of bending, were determined using ASTM D790-10 (published in April 2010).
[0362] Environmental stress cracking resistance (ESCR) Sheets molded from polyethylene compositions were tested according to the following ASTM method: Flexural resistance to environmental stress cracking (ESCR), ASTM D1693; using 100% IGEPEAL CO-630 (branched nonylphenoxy poly(ethylene oxy)ethanol, having formula 4-(branched C9H) 19 )-Phenylacetyl-[OCH2CH2] n -OH, where the subscript n is 9-10) solution and 10% IGEPALC-630 solution are used for ESCR testing under ASTM D1693 "B" conditions (at 50°C). Technicians will recognize that the test using a 10% solution ("B") 10 ") compared to the test using a 100% solution ("B") 100 () is more stringent; that is, B 10 Values are usually lower than B 100 value.
[0363] Sheets molded from polyethylene compositions were tested according to the following ASTM method: Flexural resistance to environmental stress cracking (ESCR), ASTM D1693; using 100% IGEPEAL CO-630 (branched nonylphenoxy poly(ethylene oxy)ethanol, having formula 4-(branched C9H) 19 )-Phenylacetyl-[OCH2CH2] n -OH, where the subscript n is 9-10) solution and 10% IGEPALC-630 solution are used for ESCR testing under ASTM D1693 "A" conditions (at 50°C). Technicians will recognize that the test using a 10% solution ("A") 10 ") compared to the test using a 100% solution ("A") 100 () is more stringent; that is, A 10 The value is usually lower than A 100 value.
[0364] Preparation of polyethylene compositions A polyethylene composition is prepared using a mixed dual-catalyst system in a "tandem" two-reactor solution polymerization method. As a result, the polyethylene composition comprises a first ethylene copolymer prepared using a single-site catalyst and a second ethylene copolymer prepared using a multi-site catalyst. A "tandem" two-reactor, solution-phase polymerization method, including the use of a mixed dual-catalyst, has been described in U.S. Patent Application Publication No. 2018 / 0305531. Essentially, in a "tandem" two-reactor system, the effluent stream from the first polymerization reactor (R1) flows directly into the second polymerization reactor (R2). R1 is operated at a pressure of approximately 14 MPa to approximately 18 MPa, while R2 operates at a lower pressure to facilitate continuous flow from R1 to R2. Both R1 and R2 are continuously stirred reactors (CSTRs) and are stirred to provide conditions for thorough mixing of the reactor contents. The method is operated continuously by feeding fresh process solvent, ethylene, 1-octene, and hydrogen into the reactors and removing the product. Note: In this invention, although the comonomer is not directly fed into the downstream second reactor R2 (i.e., fresh 1-octene is fed only into the first reactor R1), an ethylene copolymer is still formed in the second reactor due to the presence of unreacted 1-octene flowing from the first reactor to the second reactor (where it copolymerizes with ethylene). Methylpentane is used as the process solvent (a commercial blend of methylpentane isomers). The first CSTR reactor (R1) has a volume of 3.2 gallons (12 L), and the second CSTR reactor (R2) has a volume of 5.8 gallons (22 L). The monomer (ethylene) and comonomer (1-octene) are purified using a conventional feed preparation system (e.g., contact with various absorbent media to remove impurities such as water, oxygen, and polar contaminants) before being added to the reactors. The reactor feed is pumped to the reactors at the ratios shown in Table 1. The average residence time in the reactors is calculated by dividing the average flow rate by the reactor volume and is primarily affected by the amount of solvent flowing through each reactor and the total amount of solvent flowing through the solution method.
[0365] In the first reactor R1, the first ethylene copolymer is prepared using the following unit site catalyst (SSC) components: diphenylmethylene(cyclopentadienyl)(2,7-di-tert-butylfluorenyl)dimethylhafnium [(2,7-tBu2Flu)Ph2C(Cp)HfMe2]; methylaluminoxane (MMAO-07); triphenylmethyltetra(pentafluorophenyl)borate (triphenylmethylborate) and 2,6-di-tert-butyl-4-ethylphenol (BHEB). Methylaluminoxane (MMAO-07) is premixed online with 2,6-di-tert-butyl-4-ethylphenol and then combined with diphenylmethylene(cyclopentadienyl)(2,7-di-tert-butylfluorenyl)dimethylhafnium and triphenylmethyltetra(pentafluorophenyl)borate just before entering the polymerization reactor (R1). Suitable solvents for delivering the unit site catalyst components to the reactor include solvents such as methylpentane and o-xylene. The efficiency of the catalyst formulation per unit point is optimized by adjusting the molar ratio of the catalyst components and the inlet temperature of catalyst R1.
[0366] In a second reactor R2, a second ethylene copolymer was prepared using the following Ziegler-Natta (ZN) catalyst components: butyl ethyl magnesium; tert-butyl chloride; titanium tetrachloride; diethylaluminum ethoxide; and triethylaluminum. Methylpentane was used as the solvent for the catalyst components, and the online Ziegler-Natta catalyst formulation was prepared using the following steps and then injected into the second reactor (R2). In step one, a solution of triethylaluminum and butyl ethyl magnesium (Mg:Al = 20 mol:mol) was combined with a solution of tert-butyl chloride and allowed to react for approximately 30 seconds to produce a MgCl2 support. In step two, a titanium tetrachloride solution was added to the mixture formed in step one and allowed to react for approximately 14 seconds before being injected into the second reactor (R2). The online Ziegler-Natta catalyst was activated in the reactor by injecting the diethylaluminum ethoxide solution into R2. Table 1 shows the amount of titanium tetrachloride added to the reactor. The efficiency of the online Ziegler-Natta catalyst formulation was optimized by adjusting the molar ratio of the catalyst components.
[0367] The polymerization in the continuous solution polymerization process was terminated by adding a catalyst deactivator to the effluent stream from the second reactor. The catalyst deactivator used was octanoic acid (caprylic acid), commercially available from P&G Chemicals, Cincinnati, OH, USA. The catalyst deactivator was added such that the molar amount of the added fatty acid was 50% of the total molar amount of hafnium, titanium, and aluminum added to the polymerization process; for clarity, the molar amount of octanoic acid added = 0.5 x (molar amount of hafnium + molar amount of titanium + molar amount of aluminum).
[0368] A two-stage devolatation method is employed to recover ethylene copolymer products from the process solvent. Specifically, two vapor / liquid separators are used, with the second underflow (from a second V / L separator) passed through a gear pump / granulator combination. DHT-4V is used in the continuous solution process. ® (Hydrotalcite) [supplied by Clariant] is used as a passivating agent or acid remover. Add DHT-4V slurry in the process solvent before the first V / L separator.
[0369] Prior to granulation, the polyethylene composition is stabilized by adding approximately 500 ppm of IRGANOX 1076 (primary antioxidant) and approximately 500 ppm of IRGANOS 168 (secondary antioxidant) based on the weight of the polyethylene composition. The antioxidants are dissolved in the process solvent and added between the first V / L separator and the second V / L separator.
[0370] Table 1 shows the reactor conditions used to prepare the inventive polymer compositions (Examples 1-6) and the comparative polyethylene compositions (Examples 10, 11, 15 and 16).
[0371] Examples 1-6 of the invention and Comparative Examples 15 and 16 are ethylene-octene copolymers prepared in a pilot plant under similar conditions using a tandem two-solution polymerization mode with a single-point hafnium cadmium catalyst (“metallocene” in the table) in the first reactor (R1) and a Ziegler-Natta catalyst (“ZN” in the table) in the second reactor (R2). The melt flow ratio (I0) of Comparative Examples 15 and 16... 21 / I2) is greater than 60 (greater than the invention example).
[0372] As can be seen, Examples 4-6 were prepared using slightly different manufacturing conditions than Example 3, demonstrating the robustness of product performance to changes in manufacturing conditions, which is important in commercial operations (easier method control, better product quality).
[0373] Comparative Examples 10 and 11 were prepared in the first reactor (R1) using a phosphine imide catalyst (“phosphine imide” in the table) instead of a hafnium thallium catalyst.
[0374] Comparative Examples 7-9 and 12-14 are also described in this article.
[0375] Comparative Example 7: Commercial Rotational Molding Grade SURPASS ® RMs245-U (single-point catalyst, dual-reactor AST technology), NOVAChemicals.
[0376] Comparative Example 8: Prepared essentially according to Example 1 of US 9321865.
[0377] Comparative Example 9: Prepared essentially according to Example 3 of US 9321865.
[0378] Comparative Example 10: Prepared essentially according to Example 73 of US 9695309.
[0379] Comparative Example 11: Prepared essentially according to Example 71 of US 9695309.
[0380] Comparative Example 12: Prepared essentially according to Example 1 of US 2022 / 0396690.
[0381] Comparative Example 13: Prepared essentially according to Example 2 of US 2022 / 0396690.
[0382] Comparative Example 14: Prepared essentially according to Example 1 of WO 2021 / 250520. This is a blend of two commercial products (i.e., SURPASS RMs245 and CCs154).
[0383] Comparative Example 15: Prepared essentially according to Example 3 of WO 2022 / 195513.
[0384] Comparative Example 16: Prepared essentially according to Example 4 of WO 2022 / 195513.
[0385] The properties of the polyethylene compositions of Invention Examples 1-6 and Comparative Examples 7-16 are shown in Table 2.
[0386] As shown in Table 2, the CTREF curve of the invention is characterized by at least two peaks—specifically, a first peak eluted at a temperature above 95°C and a second peak eluted at a temperature below 90°C. Figure 1 Temperature elution fractionation curves obtained from TREF-CEF for Invention Examples 1-3 and Comparative Examples 7, 12 and 13 are shown.
[0387] Table 3 shows the key performance indicators tested on plates prepared from the exemplary polyethylene compositions, as well as the rheological properties of the exemplary polyethylene compositions. It is noteworthy that, although Example 6 has a higher melt flow index I2 (1.98 g / 10 min) and a lower average molecular weight (M) compared to Examples 3-5, it does not exhibit these properties. n M w M z However, it has been shown that ESCR performance is still maintained (because it is known that a higher melt flow index I2 or a lower molecular weight can lead to a loss of ESCR performance).
[0388] The results are discussed in more detail below with reference to the accompanying drawings.
[0389] Table 1 – Aggregation Conditions Table 1 (continued) – Aggregation Conditions Table 2 – Properties of Polyethylene Compositions Table 2 (continued) – Properties of Polyethylene Compositions Table 2 (continued) – Properties of Polyethylene Compositions Table 3 – Performance and Processing Characteristics Table 3 (continued) – Performance and Processing Characteristics Table 3 (continued) – Performance and Processing Characteristics Estimating zero-shear viscosity and rheological width parameters The viscosity data can be fitted using the following Ellis model (Eq. 7) and Carlo-Yasuda (CY) model (Eq. 8): Eq. (7) In Eq. 7, It is used as angular frequency Complex viscosity as a function of... It is zero shear viscosity. It is the characteristic relaxation time, and It is the power-law exponent.
[0390] Eq. (8) In Eq. 8, It is a complex viscosity. It is zero shear viscosity. It is the characteristic relaxation time. It is the transition width between the Newtonian plateau and the power-law region, and It is the power-law exponent. In some literature, it is referred to as the "rheological width parameter" or simply the "parameter," and it is proportional to the width of the polydispersity index or molecular weight distribution. A steeper transition indicates a narrower molecular (weight) distribution.
[0391] Dow Rheological Index (DRI) The DRI estimate measures the bias in the estimation of zero-shear viscosity and characteristic relaxation time caused by the presence of long-chain branching. Resins with a narrow molecular weight distribution and no long-chain branching are expected to have values close to zero. High DRI values can be attributed to the presence of LCBs if the material has a narrow molecular weight distribution.
[0392] Reference: S. Lai, TA Plumley, TI Butler, GW Knight, and CI Kao, DowRheology Index (DRI) for Insite Technology Polyolefins (ITP): UniqueStructure-Processing Relationships, ANTEC (San Francisco) May 1-5, 1994:1814-1815.
[0393] Relaxation Spectrum Index (RSI) The chain mobility of polymer molecules can be characterized by relaxation time spectra. Union Carbide introduced the relaxation index (RSI) based on discrete relaxation spectra. The RSI is sensitive to changes in molecular weight, molecular weight distribution, and long-chain branching.
[0394] refer to: M. Baumgaertel, HH Winter, Interrelation between continuous and discrete relaxation time spectra, Journal of Non-Newtonian Fluid Mechanics, 1992, 44: 15-36.
[0395] GPC-FTIR results Figure 2 The molecular weight distribution and comonomer distribution from GPC-FTIR measurements are shown. Examples 1-3 of the invention and Comparative Examples 15 and 16 are shown in Figure A, while Examples 1-3 of the invention and Comparative Examples 7 and 10-13 are shown in Figure B.
[0396] The invention is characterized by a high molecular weight component having a branching frequency of more than 2 carbon atoms per 1000, preferably more than 4 carbon atoms per 1000.
[0397] Rheological behavior results Figure 3 The results show the rheological behavior. Specifically, in Figure 3In the figures, Figures A, B, and C show the complex viscosity curves obtained from DMA frequency scans at 190°C. Meanwhile, Figure D shows zero-shear viscosity (estimated using the Ellis model) vs. weight-average molecular weight, where the labels indicate the example numbers and the dashed lines indicate the trends for each data group.
[0398] We also used a rheological model to fit the data to obtain the various parameters summarized in Table 3 above.
[0399] The most prominent characteristic of the long-chain branching in the examples prepared using hafnium eccentricum catalysts (Inventive Examples 1-6 and Comparative Examples 15 and 16) is the wider transition width across the Newtonian plateau and power-law region, spanning a broader frequency range, compared to resins with linear molecular structures (i.e., lacking long-chain branching). The transition width of the Inventive Examples is less pronounced than that of Comparative Examples 15 and 16 (which have higher long-chain branching content). In this disclosure, the rheological width parameter α (Carlo-Yasuda model) is used to quantify the transition.
[0400] The values of the relaxation spectrum index (RSI) and the Dow rheological index (DRI) also indicate the long chain branching in the invention example, but the effect is not as obvious as in comparative examples 15 and 16.
[0401] The invention contains a small number of long-chain branches, which, compared to resins with a linear structure and otherwise comparable molecular weight distribution, results in a higher zero-shear viscosity and is believed to lead to higher melt strength (see [link]). Figure 3 (See Figure D). The presence of long-chain branching is indicated by a relatively low rheological width parameter value a (typically less than about 0.040). Higher zero-shear viscosity (i.e., higher resistance to flow at low deformation frequencies) is advantageous in the manufacture of larger rotationally molded parts (e.g., large tanks) because the heating cycles for these parts may be long and the resin carries a higher risk of causing excessive melt flow limits.
[0402] ESCR, cantilever beam impact and stiffness – discussion and results Environmental stress cracking occurs when chemical reagents permeate a material, thereby reducing its ductility and interfering with the intermolecular forces of the bonded polymer chains. The permeation of chemical reagents reduces the energy required for disentanglement and causes the failure mechanism to shift from yielding.
[0403] ESCR is a property related to the performance of containers (including containers such as medium bulk containers) in applications ranging from household applications (e.g., detergents) to many industrial applications (e.g., agriculture and chemicals). Density greater than 0.940 g / cm³ 3The ESCR performance of polyethylene resins tends to decrease with increasing density (and thus stiffness). An increase in the amount of crystalline structure may impose greater restrictions on the mobility associated with amorphous regions. However, for higher-density resins, a decrease in comonomer content also leads to a reduction in the amount of molecules binding the crystalline domains together. The concept of tethered molecules is related to crack initiation resistance by causing reduced chain mobility in amorphous regions, and thus resulting in greater resistance to chain disentanglement when the specimen is exposed to stress.
[0404] The concept of ligature molecules is also related to the efficiency of energy transfer and dissipation when the specimen is subjected to impact. When resin properties are otherwise comparable, cantilever beam and tensile impact resistance generally decrease with increasing density (stiffness). Cantilever beam measurements measure the resin's resistance to bending impact, while tensile impact measurements are performed at higher deformation rates and are used to further differentiate resins.
[0405] Figure 4 (And Table 3 above) presents the ESCR and impact performance of several comparative examples compared to Invention Examples 1-6. Figure 4 In the figure, Figure A shows the results in IGEPAL CO-630 under ESCR condition A100, while Figure B shows the cantilever beam impact, both plotted relative to the flexural secant modulus (1%).
[0406] The high performance of the invention can be attributed primarily to the incorporation of high comonomers in the high molecular weight components of these polymer compositions. This follows the general principle of improving ESCR and toughness based on the concept of chalcedony. The increase in molecular weight, along with the increase in comonomer incorporation, promotes the formation of chalcedony.
[0407] When resin properties are otherwise comparable, cantilever beam impact typically decreases with increasing density (stiffness). A similar trend was observed between ESCR and stiffness within the density range considered in this paper for rigid molding applications. Figure 4 As shown, for the examples prepared using hafnium eccentricum catalysts (Invention Examples 1-6 and Comparative Examples 15 and 16), the trend of cantilever beam impact vs. stiffness shifts to higher values.
[0408] Compared to the comparative examples, the inventive examples demonstrate a superior combination of ESCR, cantilever beam impact, and stiffness. Higher cantilever beam impact performance is typically observed when other aspects of stiffness are comparable (see, for example, Comparative Examples 7, 13, and 14).
[0409] Rotational molding component preparation A rotary molding machine (specifically, a Rotospeed RS160 available from Ferry Industries Inc. (Stow, Ohio, USA)) was used to convert powdered polyethylene composition into rotational molded parts. The Rotospeed has two arms that rotate about a central axis within a closed oven. Each arm is fitted with a plate that rotates on an axis substantially perpendicular to the arm's axis of rotation. Each arm is fitted with six cast aluminum molds that produce hollow, cubic rotational molded parts, i.e., 12.5 inches (31.8 cm) × 12.5 inches × 12.5 inches. The arm rotation was set to approximately 8 revolutions per minute (rpm), and the plate rotation was set to approximately 2 rpm. A standard charge of approximately 3.7 kg of the polyethylene composition in powder form was used to produce rotational molded parts with a nominal thickness of approximately 0.250 inches (0.64 cm), wherein the powder has a 35 US mesh size (screen opening of 0.0197 inches (500 μm)). The temperature within the closed oven was maintained at 560℉ (293°C). The mold and its contents were heated in an oven for 18, 20, 22, 24, and 26 minutes to ensure complete powder densification. The mold was then cooled with a fan for approximately 30 minutes before the part was removed. After removal, the plastic part was kept at room temperature for at least 24 hours before being cut to collect specimens for subsequent testing. Specimens were collected from the molded part for density evaluation and ARM impact testing.
[0410] ARM stress test The ARM impact test is performed according to ASTM D5628 at a test temperature of −40°C. This test is adapted from the Association of Rotational Molders International, Low Temperature Impact Test, version 4.0 (dated July 2003). The purpose of this test is to determine the impact performance of rotomolded parts. ARM impact test specimens (5 inches × 5 inches (12.7 cm × 12.7 cm)) are cut from the sidewall of a cubic rotomolded part. The test specimens are kept at −40℉ ± 3.5℉ (−40°C ± 2°C) in a refrigerated test laboratory for at least 24 hours to achieve thermal equilibration, after which the impact test is performed. The test technique used is commonly referred to as the Brucellstone step method or the up-and-down method. This procedure establishes a specific dart height that will cause 50% of the specimens to fail; that is, the test is performed (darts fall on the specimen) until at least 10 passes and 10 failures. Each failure is characterized as either ductile or brittle failure. Ductile failure is characterized by dart penetration of the specimen, and elongation and thinning of the impact area, leaving a hole with fibrous structures at the failure point. Brittle failure is evident when the test specimen cracks, with cracks radiating outward from the failure point, and the specimen exhibiting minimal to no elongation at the failure point. The “ARM ductility %” is calculated as follows: 100% × [(number of ductile failures) / (total number of all failures)].
[0411] The samples were subjected to impact testing using a drop hammer impact testing machine; available impact darts consisted of 10 lb (4.54 kg), 15 lb (6.80 kg), 20 lb (9.07 kg), or 30 lb (13.6 kg) darts. All impact darts had a rounded tip with a diameter of 1.0 ± 0.005 inches (2.54 cm), transitioning to a lower cylindrical shaft (1.0 inch in diameter) with a length of 4.5 inches (11.4 cm) from the tip. The impact darts also included an upper cylindrical shaft with a diameter of 2.0 inches (5.08 cm), the length of which varied depending on the desired weight of the dart; for example, it was 10.5 inches (26.7 cm) for a 10 lb dart and 16.5 inches (41.9 cm) for a 20 lb dart. Preferably, the dart weight is selected such that the drop height is between 2.5 ft and 7.5 ft (0.8 m–2.3 m). The test specimen is oriented in an impact testing machine such that the dart impacts the surface of the component in contact with the mold (during molding). If the specimen does not fail at a given height and weight, the height or weight is increased until component failure occurs. Once failure occurs, the height or weight is decreased by the same increment, and the process is repeated. The “ARM mean failure energy (ft·lb)” is calculated by multiplying the drop height (ft) by the nominal dart weight (lb). After impact, failure is examined on both the upper and lower surfaces of the specimen. For the polyethylene compositions disclosed herein, ductile failure is the desired failure mode.
[0412] Rotational molding processability and performance window results Good rotational molding performance is characterized by a combination of high average failure energy (>100 ft·lb) and high ductility (>50%) in the parts. Processability and processing window are defined by the width of the range of oven dwell times that provide good performance when molding conditions are otherwise constant (mold, part thickness, oven temperature).
[0413] Figure 5 Results of tests conducted on rotationally molded specimens (collected from 1 / 4-inch thick test cubes rotated at an oven temperature of 293°C (560°F); see above for more details on the preparation of rotationally molded parts) are presented. Figure 5 In the figure, Figures A and B show the mean failure energy of ARM impact at −40°C; Figures C and D show the ductility at −40°C; and Figures E and F show the difference between the original rotational molding density and the sheet density (ASTM D792-13).
[0414] As can be seen, Examples 1-3 exhibit processing windows comparable to or better than those of commercial rotational molding grades (Comparative Example 7). Examples 1-3 exhibit processing windows superior to those of Comparative Examples 15 and 16. This can be attributed to the more favorable rheology (lower zero-shear viscosity) of the examples. Lower zero-shear viscosity facilitates neck growth (sintering) between powder particles during the melt densification process. Better sintering results in the formation of smaller bubbles, which then dissolve into the melt at a faster rate. Faster sintering and bubble dissolution are important for ensuring that melt densification is completed within the molding cycle. If not completed, bubbles remain in the molded part, thus becoming defects and leading to deterioration of mechanical properties.
[0415] Despite the presence of air bubbles in the molded part (due to short oven time), the inventive examples still maintain good performance. Air bubbles are inferred when the original density of the molded specimen is significantly lower than the sheet density (ASTM D792-13). Interestingly, it is noted that although densification is slower than Comparative Example 7, the disclosed examples exhibit excellent impact properties (mean failure energy and ductility). This result suggests that the inventive examples can tolerate higher levels of defects within the molded part while still providing good toughness.
[0416] For Examples 1 and 2, the additive package formulation used in the rotational molding test contained 384 ppm of hydroxylamine (IRGASTAB FS 042) by weight. Example 3 was formulated using two levels of IRGASTAB FS 042. Figure 5 The changes in the additive package shown in the results of Example 3 of the invention, specifically the increase in the hydroxylamine content from 384 ppm by weight (labeled "conventional additive") to 800 ppm by weight (labeled "alternative additive"), resulted in a significant improvement in performance and powder densification. This can... Figure 5 The curves for mean failure energy, ductility, and original density versus oven dwell time show a significant shift towards achieving higher ductility and failure energy, as well as higher densification.
[0417] Some additives were added in masterbatch form, while others were added in powder form. Additives in masterbatch form were melt-blended in Examples 1 and 2 using a Coperion ZSK26 twin-screw extruder. Additives were added in Example 3 using a Leistritz LSM30.34 twin-screw extruder. Conventional additive formulations were prepared by adding masterbatch-form additives via melt blending. Alternative additive formulations used a combination of masterbatch and selected additives supplemented using powder form. When additives were added in powder form, the powdered additive was first combined with a portion of the base resin, also in powder form, to ensure accurate additive weighing throughout the sample.
[0418] Deconvolution of polyethylene composition For Examples 1-6 of the invention, mathematical deconvolution is performed to determine the relative amounts of the first ethylene copolymer and the second ethylene copolymer (and, when present in the comparative examples, the third ethylene copolymer) in the polyethylene composition, as well as the molecular weight (M) of each copolymer. w M n M z The data included the comonomer content (SCB frequency / 1000 polymer backbone carbon atoms). For deconvolution calculations, it was assumed that the ethylene copolymer components catalyzed at a single point followed the Florey molecular weight distribution function and that they had a uniform comonomer distribution across the entire molecular weight range. The ethylene copolymer components prepared using a Ziegler-Natta type catalyst were modeled as a combination of four catalytic sites, each following the Florey molecular weight distribution function. For the comparative examples (Examples 10 and 11), the data provided in Table 4 are as previously reported in US 9695309.
[0419] First, estimates were obtained from predictions using a basic kinetic model with kinetic constants specific to each catalyst formulation and feed and reactor conditions. Simulations were based on a solution-based pilot-scale apparatus configuration as described above, used to produce the polyethylene compositions disclosed herein. Kinetic model predictions were used to establish estimates of the short-chain branching distribution within the first and second ethylene copolymer components. Estimates of the short-branch content were also validated against experimental results obtained from GPC-FTIR of the comonomer distribution. Fitting the simulated molecular weight distribution curves to actual data obtained from GPC chromatography was improved by modeling the molecular weight distribution as the sum of components with a molecular weight distribution described using a multi-site idealized Flory distribution.
[0420] During deconvolution, the following relationship is used to calculate the population M. n M w and M z : Mn = 1 / ∑(w i / (M n ) i M w =∑(w i x (M w ) i M z =∑(w i x (M z ) i 2 / ∑(w i x (M zi ) Where i represents the i-th component, and w i This represents the relative weight fraction of the i-th component in the composition.
[0421] The following equations are used to calculate the density and melt index (I2) of each ethylene copolymer component: Eq. (9) Eq. (10) Eq. (11) Where M n M w M z SCB / 1000C are the deconvolution values of the individual ethylene polymer components obtained from the deconvolution results described above, while ρ This is the density of the total polyethylene composition and was determined experimentally. Equations (9) and (10) are used to estimate... ρ1 and ρ2 (Density of the first and second ethylene copolymers). Equation (11) is used to estimate the melt index (I2) of each of the first and second ethylene copolymers. See, for example, Alfred Rudin's... The Elements of Polymer Science and Engineering , 2nd edition, Academic Press, 1999 and U.S. Patent No. 8,022,143.
[0422] The molecular weight deconvolution results are provided in Table 4, which shows Invention Examples 1-6 and comparative examples (Examples 10 and 11) with the closest compositions.
[0423] Table 4 – Deconvolution of Polyethylene Compositions Industrial applicability A polyethylene composition suitable for use in rotationally molded plastic products is presented. This polyethylene composition exhibits a good combination of environmental stress cracking resistance, cantilever beam impact strength, and stiffness when formed into sheets.
Claims
1. A polyethylene composition comprising: (i) 10 to 60 wt% of a first ethylene copolymer having a density of 0.880 to 0.930 g / cm 3 , a molecular weight distribution (M w / M n ) of 1.7 to 2.7, and a weight average molecular weight (M w ) of 140,000 to 250,000 g / mol; (ii) 90 to 40 weight percent of a second ethylene copolymer having a density of 0.940 to 0.975 g / cm 3 , a molecular weight distribution (M w / M n ) of 2.0 to 3.3, and a weight average molecular weight (M w ) of 20,000 to 90,000 g / mol; wherein the ratio of the number of short chain branches per thousand carbon atoms in the first ethylene copolymer to the number of short chain branches per thousand carbon atoms in the second ethylene copolymer (SCB1 / SCB2) is at least 5.0; wherein the polyethylene composition has a density of at least 0.940 g / cm 3 , a melt index (I2) of less than 3.0 g / 10 min, a melt flow ratio (I 21 / I2) of at most 60, and a long chain branching factor (LCBF) of at most 0.0400; and wherein the weight percent of the first ethylene copolymer or second ethylene copolymer is defined as the weight of the first copolymer or second copolymer, respectively, divided by the sum of the weight of the first ethylene copolymer and the second ethylene copolymer, multiplied by 100.
2. The polyethylene composition of claim 1, wherein the LCBF of the polyethylene composition is from 0.0050 to 0.0375.
3. The polyethylene composition of claim 1 or claim 2, wherein the polyethylene composition has a melt flow ratio (I 21 / I2) of 20 to 50.
4. The polyethylene composition of any one of claims 1-3, wherein the polyethylene composition has a molecular weight distribution (M w / M n ) of less than 4.
5.
5. The polyethylene composition of claim 4, wherein the polyethylene composition has a molecular weight distribution (M w / M n ) of 2.0-4.
0.
6. The polyethylene composition of any one of claims 1-5, wherein the polyethylene composition has a unimodal distribution in GPC analysis.
7. The polyethylene composition of any one of claims 1-6, wherein the first ethylene copolymer has a density of 0.890-0.925 g / cm 3 .
8. The polyethylene composition of any one of claims 1-7, wherein the first ethylene copolymer has a melt index (I2) of at most 1.0 g / 10 min.
9. The polyethylene composition of claim 8, wherein the first ethylene copolymer has a melt index (I2) of from 0.001 to 0.7 g / 10 min.
10. The polyethylene composition of any one of claims 1-9, wherein the second ethylene copolymer has a melt index (I2) of at least 2.0 g / 10 min.
11. The polyethylene composition of claim 10, wherein the second ethylene copolymer has a melt index (I2) of from 2.0 to 50 g / 10 min.
12. The polyethylene composition of any one of claims 1-11, wherein the polyethylene composition has a density of 0.942 to 0.957 g / cm3 3 .
13. The polyethylene composition of claim 12, wherein the polyethylene composition has a density of 0.945 to 0.955 g / cm3 3 .
14. The polyethylene composition of any one of claims 1-13, wherein the polyethylene composition has a melt index (I2) of from 1.0 to 2.6 g / 10 min.
15. The polyethylene composition of any one of claims 1-14, wherein the polyethylene composition has a high load melt index (I 21 ) of at least 30 g / 10 min.
16. The polyethylene composition of claim 15, wherein the polyethylene composition has a high load melt index (I 21 ) of 30 to 100 g / 10 min.
17. The polyethylene composition of any one of claims 1-16, wherein the polyethylene composition has a weight average molecular weight (M w ) of 70,000-120,000 g / mol.
18. The polyethylene composition of any one of claims 1-17, wherein the polyethylene composition has a number average molecular weight (M n ) of 20,000-40,000 g / mol.
19. The polyethylene composition of any one of claims 1-18, wherein the polyethylene composition has a Z-average molecular weight (M z ) of less than 400,000 g / mol.
20. The polyethylene composition of claim 19, wherein the polyethylene composition has a Z-average molecular weight (M z ) of 100,000 to 350,000 g / mol.
21. The polyethylene composition of any one of claims 1-20, wherein the polyethylene composition has a M z / M w of less than 3.
3.
22. The polyethylene composition of claim 21, wherein the polyethylene composition has a Mw z / M w of 1.5-3.
0.
23. The polyethylene composition of any one of claims 1-22, wherein the polyethylene composition has hafnium from 0.0015 to 2.4 ppm.
24. The polyethylene composition of any one of claims 1-23, wherein the first ethylene copolymer has from 2 to 30 short chain branches per thousand carbon atoms (SCB1 / 1000C).
25. The polyethylene composition of claim 24, wherein the first ethylene copolymer has from 4 to 25 short chain branches per thousand carbon atoms (SCB1 / 1000C).
26. The polyethylene composition of any one of claims 1-25, wherein the second ethylene copolymer has from 0.05 to 3 short chain branches per thousand carbon atoms (SCB2 / 1000C).
27. The polyethylene composition of any one of claims 1-26, wherein the ratio of the number of short chain branches per thousand carbon atoms in the first ethylene copolymer to the number of short chain branches per thousand carbon atoms in the second ethylene copolymer (SCB1 / SCB2) is at least 10.
28. The polyethylene composition of any one of claims 1-27, wherein the polyethylene composition has a fraction eluting at higher than 95 °C in CTREF analysis.
29. The polyethylene composition of any one of claims 1-28, wherein the polyethylene composition has a fraction eluting below 90°C in a CTREF analysis.
30. The polyethylene composition of any one of claims 1-29, wherein the polyethylene composition has a rheology breadth parameter (a) of less than 0.400 as measured by the Carreau-Yasuda model.
31. The polyethylene composition of any one of claims 1-30, wherein the polyethylene composition has an environmental stress crack resistance (ESCR) of greater than 500 hours as determined by ASTM D1693 in 100% IGEPAL CO-630 under Condition A.
32. The polyethylene composition of claim 31, wherein the polyethylene composition has an environmental stress crack resistance (ESCR) of greater than 1000 hours as determined by ASTM D1693 in 100% IGEPAL CO-630 under Condition A.
33. The polyethylene composition of any one of claims 1-32, wherein the polyethylene composition has an environmental stress crack resistance (ESCR) of greater than 50 hours as determined by ASTM D1693 in 10% IGEPAL CO-630 under Condition A.
34. The polyethylene composition of claim 33, wherein the polyethylene composition has an environmental stress crack resistance (ESCR) of greater than 100 hours as determined by ASTM D1693 in 10% IGEPAL CO-630 under Condition A.
35. The polyethylene composition of any one of claims 1-34, wherein the polyethylene composition has a Charpy impact value of at least 4.0 ft-lb / in.
36. The polyethylene composition of claim 35, wherein the polyethylene composition has a Charpy impact value of 4.0-13.0 ft-lb / in.
37. The polyethylene composition of claim 35 or claim 36, wherein the polyethylene composition has a Charpy impact value of at least 6.0 ft-lb / in.
38. The polyethylene composition of any one of claims 1-37, wherein the polyethylene composition has a tensile impact value of at least 230 foot-pounds / inch 2 .
39. The polyethylene composition of any one of claims 1-38, wherein the polyethylene composition has a flexural secant modulus at 1% of at least 1000 MPa.
40. The polyethylene composition of claim 39, wherein the polyethylene composition has a flexural secant modulus at 1% of 1000-1300 MPa.
41. The polyethylene composition of any one of claims 1-40, wherein the polyethylene composition has an elasticity ratio (G’ / G”) at 0.05 rad / s of at most 0.
25.
42. A solution phase polymerization process to make a polyethylene composition; wherein the solution phase polymerization process comprises: polymerizing ethylene and alpha-olefins in a first reactor with a metallocene catalyst; and polymerizing ethylene and alpha-olefins in a second reactor with a Ziegler-Natta catalyst; wherein the first reactor and the second reactor are arranged in series with each other; and wherein the polyethylene composition comprises: (i) 10 to 60 wt% of a first ethylene copolymer having a density of 0.880 to 0.930 g / cm 3 , a molecular weight distribution (M w / M n ) of 1.7 to 2.7, and a weight average molecular weight (M w ) of 140,000 to 250,000 g / mol; (ii) 90 to 40 weight percent of a second ethylene copolymer having a density of 0.940 to 0.975 g / cm 3 , a molecular weight distribution (M w / M n ) of 2.0 to 3.3, and a weight average molecular weight (M w ) of 20,000 to 90,000 g / mol; wherein the ratio of the number of short chain branches per thousand carbon atoms in the first ethylene copolymer to the number of short chain branches per thousand carbon atoms in the second ethylene copolymer (SCB1 / SCB2) is at least 5.0; wherein the polyethylene composition has a density of at least 0.940 g / cm 3 , a melt index (I2) of less than 3.0 g / 10 min, a melt flow ratio (I 21 / I2) of at most 60, and a long chain branching factor (LCBF) of at most 0.0400; and wherein the weight percent of the first ethylene copolymer or second ethylene copolymer is defined as the weight of the first copolymer or second copolymer, respectively, divided by the sum of the weight of the first ethylene copolymer and the second ethylene copolymer, multiplied by 100.
43. A rotational molded article prepared from a polyethylene composition comprising: (i) 10 to 60 wt% of a first ethylene copolymer having a density of 0.880 to 0.930 g / cm 3 , a molecular weight distribution (M w / M n ) of 1.7 to 2.7, and a weight average molecular weight (M w ) of 140,000 to 250,000 g / mol; (ii) 90 to 40 weight percent of a second ethylene copolymer having a density of 0.940 to 0.975 g / cm 3 , a molecular weight distribution (M w / M n ) of 2.0 to 3.3, and a weight average molecular weight (M w ) of 20,000 to 90,000 g / mol; wherein the ratio of the number of short chain branches per thousand carbon atoms in the first ethylene copolymer to the number of short chain branches per thousand carbon atoms in the second ethylene copolymer (SCB1 / SCB2) is at least 5.0; wherein the polyethylene composition has a density of at least 0.940 g / cm 3 , a melt index (I2) of less than 3.0 g / 10 min, a melt flow ratio (I 21 / I2) of at most 60, and a long chain branching factor (LCBF) of at most 0.0400; and wherein the weight percent of the first ethylene copolymer or second ethylene copolymer is defined as the weight of the first copolymer or second copolymer, respectively, divided by the sum of the weight of the first ethylene copolymer and the second ethylene copolymer, multiplied by 100.
44. The rotational molded article of claim 43, wherein the polyethylene composition contains an additive package comprising: a hindered mono-phosphite; a di-phosphite; a hindered amine light stabilizer; and at least one additional additive selected from the group consisting of hindered phenols and hydroxylamines.
45. The rotational molded article of claim 44, wherein the hydroxylamine of the additive package is N,N-dialkylhydroxylamine, preferably IRGASTAB FS 042.
46. The rotational molded article of claim 45, wherein the hydroxylamine is present at a concentration of at least about 750 ppm by weight.
Citation Information
Patent Citations
Means for increasing the molecular weight and decreasing the density employing mixed homogeneous catalyst formulations
US10442921B2
Polyethylene compositions and articles made therefrom
US10808053B2
Means For Increasing the Molecular Weight and Decreasing the Density of Ethylene Interpolymers Employing Homogeneous and Heterogeneous Catalyst Formulations
US20180305531A1
Linear high-density polyethylene with high toughness and high escr
US20220396690A1
Crystalline synthetic resin composition
US5342868A